Postharvest control of Botryosphaeria dothidea-induced pear ring rot by Chrysanthemum indicum essential oil: Composition, efficacy, and mechanistic insights - Bin Wang; Sha-Sha Liu; Jia-Ying Wu; Meng-Ran Yu; Yun-Kai Lv; Jian Wang; Li-Juan Wang; Fei Cao (Postharvest Biology and Technology, 2026)

Insights into spring dust aerosol trends over North China from CMIP6 historical simulations and multi-source observations - Tong Sha; Haoxuan Li; Jingda Liu; Guiqian Tang; Yuesi Wang (Atmospheric Research, 2026)

Yam glycoprotein mediated the immunomodulation of macrophages by targeting TLR4 - Yuzhi Luo; Siqi Wang; Lingyi Liu; Ruisi Zhu; Xiaoyue Wang; Yajing Ma; Huixin Song; Sha Wen; Lingli Li; Songyuan Xia; Weifeng Li; Xiaofeng Niu (Molecular Biology Reports, 2026)

Recharge sources and genesis of underground brines in the Mahai Basin, Qaidam Basin, China: insights from hydrochemistry and multi-isotope tracers - Ruibo Liu; Xiwei Qin; Wenquan Lu; Haiyan Shi; Zhen Shi; Chenglin Liu; Ying Ma; Xiangjun Li; Sha Yang; Ziwen Jiang; Genhou Wang; Ming Ma; et al. (Carbonates and Evaporites, 2026)

pH regulation of 1,2-bis(trimethoxysilyl)ethane hydrolysis pathways for enhanced wet state stability of TEMPO-oxidized cellulose nanofiber aerogels - Aojia Zhang; Rui Teng; Quan Zhang; Xue Liu; Biyao Sun; Chengcheng Suo; Sha Luo; Chunhui Ma; Shouxin Liu; Wei Li (Carbohydrate Polymers, 2026)

Poly(phenol-imidazole) nanosheets engineered multifunctional hydrogel for promotion of infected diabetic wound healing - Jia Xin Yu; Lu Yao Li; Yu Fan; Piao Zheng; Sha Yang; Qi Fang Liu; Cai Juan Huang; Ya Lin Cao; Yang You (Chemical Engineering Journal, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Resistant starch nanoparticles: Navigating the trade-offs between fabrication, structure, and function - Chao Ding; Li-Na Liu; Sha Yang (Food Chemistry, 2026)

HYDRA-EDGE: HYDrogel-based rapid assay with entropy-driven gel enhancement for point-of-care viral detection - Ailing Yang; Li Zhou; Jing Li; Yu Liu; Ting Xiao; Qingxiang Yang; Dunquan Xu; Jiezhong Deng; Ming Chen; Sha Yang (Chemical Engineering Journal, 2026)

Vortex bionic structural composites fabricated by DLP 3D printing with high electromagnetic shielding effect and thermal conductive property - Jingxing Gui; Tao Zhang; Sha Long; Yingtao Li; Feiyue Zhou; Yuxuan Ma; Yuting Xue; Xueting Xu; Chunyan Hu; Baojiang Liu; Dan Yu; Wei Wang (Chemical Engineering Journal, 2026)

Honokiol Ameliorates Pyroptosis in Bovine Mammary Epithelial Cells via SIRT3-Mediated Inhibition of the NLRP3 Inflammasome - Sha Tang; Yanqiong Wen; Renxin Wu; Xing Shi; Dan Li; Siqing Mao; Xiao Yang; Hang Yu; Lei Tian; Le Zhang; Lei Liu (Tissue and Cell, 2026)

Functional exploration of mitochondrial carrier family proteins in faba bean for drought tolerance improvement - Zi-Hua Zhang; Chang-Yan Liu; Hong-Wei Chen; Li Li; Yong-Guo Zhao; Xiao-Jiao Xiang; Wen-Hui Wei; Ai-Hua Sha (Plant Science, 2026)

The SeABI5 transcription factor couples ABA signaling with flavonoid antioxidant production to confer cadmium tolerance in Salicornia europaea - Jinchao Zhou; Pengtao Ji; Guangli Liu; Shuanghong Wang; Lu Liu; Chenyi Liu; Guangyu Sun; Sha Xue; Youwei Du; Huike Li (Journal of Hazardous Materials, 2026)

Engineered extracellular vesicle-based microneedle patch via nose-to-brain delivery for enhanced treatment of Alzheimer's disease - Chengxue Pan; Sha Liu; Yue Zhang; Yunxia Li; Linlin Cao; Junli Zhang (Chemical Engineering Journal, 2026)

Engineering exposed crystal planes of ZIF-8 to tune the surface coordination environment for stable zinc metal anodes - Yao Dai; Wenhao Li; Huilin Fan; Runguo Zheng; Zhiyuan Wang; Sha Liu; Hongyu Sun; Yanguo Liu (Chemical Engineering Journal, 2026)

Mussel-inspired molecular strategy for ultrasensitive detection of multiple chiral molecules - Yanhong Liu; Yang Li; Chengcheng Suo; Wei Li; Sha Luo; Chunhui Ma; Shouxin Liu (Analytica Chimica Acta, 2026)

Online proteolysis and specific affinity enrichment of ACE inhibitory peptides on a magnetic nanoplatform from Torreya grandis protein - Kexin Liu; Jiajun Cui; Ke Xu; Jiaqi Zheng; Yixuan Xiao; Lin Chen; Sha Li; Jiyou Yang; Hongying Guo; Xin Wang; Fei Gao; Jie Li; et al. (Food Chemistry, 2026)

Injectable adhesive hydrogel with self-assembled dual-enzyme nanofibers for spatiotemporal modulation of inflammation and axon regeneration after spinal cord injury - Qi Sha; Yuan Li; Zuomeng Wu; Yankai Wang; Yunxiao Fang; Ao Liu; Shunfeng Liu; Yixiang Dong; Lu Ye; Yue Qin; Shuhui Sun; Junjie Zhao; et al. (Chemical Engineering Journal, 2026)

Lattice distortion and electronic synergy in Al/Zn-modified ultrathin high-entropy oxides towards unlocking efficient water splitting - Junyuan Yang; Yachao Xu; Sha Gong; Nuo Liu; Liangyu Wu; Donghao Cao; Zehua Guo; Zheng Li; Long Gu; Yunhe Zhao (Chemical Engineering Journal, 2026)

Secondary disinfection strategies regulate chemical risk and microbial community assembly in secondary water supply systems - Sha Feng; Xing Li; Yongwang Liu; Zedong Lu; Na Li; Yuanrong Qiu; Li Zhao (Chemical Engineering Journal, 2026)

Plant growth patterns serve as a power switch governing microbial N use efficiency and N2O emission in an alpine meadow under climate change on the Qinghai-Tibet Plateau - Zheng Li; Yubao Sha; Huihui Liu; Guozheng Hu; Fen Zhao; Hasbagan Ganjurjav; Qingzhu Gao (Agriculture, Ecosystems & Environment, 2026)

The gut microbiota mediates the antidepressant effects of imipramine: Evidence from fecal microbiota transplantation and prebiotic inulin intervention - Yonglan Chen; Yuxin Lan; Jingyan Yi; Xiaoyi Qi; Li Liu; Sha Liu; Xinxin Xu; Huan Liu; Yufeng He; Bing He; Xiaochi Ma; Muhan Lü; et al. (Psychopharmacology, 2026)

B-MARCO: a blockchain-driven multi-national auction and resource optimization framework for cross-border logistics and trade - Mei Sha; Shuang Li; Tao Zhang; Han Liu; Jianli Shen; Xiaohu Huang; Jiahua Hu (Frontiers in Marine Science, 2026)
Cross-border maritime logistics requires coordination among carriers, ports, customs authorities, and financial institutions, yet existing workflows are often constrained by fragmented regulatory data systems, inefficient dynamic capacity matching, and slow batch-based clearing. This paper proposes B-MARCO, a blockchain-driven multi-national auction and resource optimization framework for cross-border maritime logistics. B-MARCO integrates permissioned consortium coordination, rolling auction-based market clearing, a hybrid GA-GSA dispatching engine, and privacy-preserving access-control and compliance-verification components. The evaluation uses a semi-synthetic discrete-event simulation with a 7-day horizon, hourly decision intervals, 30 random seeds, and shared order streams across all configurations. Under a 5,000-orders/day workload, B-MARCO achieves a 91.80% transaction success rate and 21.53 h average end-to-end latency, compared with 60.09% and 36.66 h for the 24-hour batch-clearing baseline. Relative to a centralized rolling-matching baseline, it reduces average latency by 13.60%. The ablation results show that rolling auction clearing reduces latency, while smart-contract-based settlement-delay reduction is a major contributor to improved success and deadline performance. These findings support the value of combining rolling market clearing with spatial-temporal dispatch optimization in simulated cross-border maritime logistics, while the blockchain and cryptographic modules define the broader coordination, auditability, and data-governance architecture.

TREM2 mediates macrophage suppression of NLRP3 inflammasome pathway to promote non-small cell lung cancer progression - Ruocheng Sha; Haonan Wang; Peili Chen; Xuemei Wei; Haoyi Li; Zhongzheng Jiang; Chenyang Liu; Mingming Liu; Fengming Tian; Xiumin Ma (Molecular and Cellular Biochemistry, 2026)

Quantifying the light interception and canopy photosynthesis of strip intercropping system based on 3D canopy photosynthesis model - Si-Rong Huang; Qing-Feng Song; Zheng Guo; Qiu-Feng Long; Li-Sha Zhang; Yue Li; Yuan Yang; Xiao-Chun Wang; Feng Yang; Tai-Wen Yong; Jiang Liu; Yan-Hong Yan; et al. (Computers and Electronics in Agriculture, 2026)

Enhanced deep nitrogen removal from low C/N wastewater via manganese-catalyzed iron-carbon micro-electrolysis coupled biological system: performance, mechanism, and microbial adaptability - Hengyuan Liu; Kai Wang; Feng Sha; Haibing Che; Rui Sun; Xiuhua Li (World Journal of Microbiology and Biotechnology, 2026)

Genome-wide insights into the regulatory networks of ZmHsf28 in salt and drought stress - Lijun Liu; Xia Zheng; Xiaoyu Sha; Shuaibing Tian; Ziyi Luo; Yuhan Zhang; Guocheng Wei; Yuxin Li; Jingye Fu; Qiang Wang (Plant Science, 2026)

Secondary chlorination enhanced the role of pipe materials in shaping chlorine-resistant microbiome and antibiotic resistome in secondary water supply systems - Yuanrong Qiu; Yanling Yang; Na Li; Xing Li; Zedong Lu; Zhiwei Zhou; Sha Feng; Yongwang Liu (Journal of Hazardous Materials, 2026)

Precise prevention of DEHP induced hepatic fibrosis: Early identifying high-risk populations, revealing key factors, and applying targeted intervention - Xinru Du; Moyan Wang; Zhendong Wang; Ziyan Xue; Yancheng Gao; Yue Ma; Ziyi Wang; Sha Liu; Mengyue Ji; Ye Yang; Chunxiao Zhou; Yuan Li (Journal of Environmental Sciences, 2026)

Bidirectional interfacial polymerization-architected nanoporous graphene-polyamide nanofilms for efficient antibiotic separation - Yumin Sun; Yongbo Yang; Sha Liang; Yihang Zhang; Qinglin Huang; Xutong Han; Changfa Xiao; Wei Li; Kaikai Chen; Xianhui Li; Yang Yang; Hailiang Liu (Chemical Engineering Journal, 2026)

Co-Pyrolysis of Titanium Gypsum and Cow Dung to Prepare Modified Biochar for Phosphorus Adsorption in Water - Dongyi Li; He Li; Zhigang Liu; Kexin Xu; Pengfei Wu; Aiguo Sha; Fan Li (Water, Air, & Soil Pollution, 2026)

Peroxisome proliferator-activated receptor γ coordinates the “growth-defense trade-off” in intensive aquaculture of grass carp (Ctenopharyngodon idella) - Wenting Huang; Shaoqing Zang; Hui Liu; Xinlu Ren; Ruixue Zhang; Yu Yang; Wenwen Wang; Suxu Tan; Tingting Li; Kunpeng Shi; Zhenxia Sha (Aquaculture, 2026)

Speciated emissions of full-volatility organic compounds from plastic manufacturing: atmospheric impacts and toxicity generation - Dongyang Wu; Qing’e Sha; Luyun Liu; Citao Zhang; Shan Jiang; Qing Guo; Junhao Xu; Jialin Song; Renjun Li; Liufen Cai; Haoqi Chen; Guanghui Li; et al. (Journal of Environmental Sciences, 2026)

Distribution characteristics, source apportionment and risk assessment of heavy metal pollution in typical redevelopment sites in Jinshan District, Shanghai, China - Cheng Shen; Chenyan Sha; Tianhao He; Zhongchun Yan; Xiurong Chen; Kuangfei Lin; Haichao Chen; Jian Wu; Ye Li; Min Liu (Journal of Environmental Sciences, 2026)

Castor oil-based waterborne polyurethane photodynamic antimicrobial films: Preparation and strawberry preservation application - Zhanpeng Zhu; Li Liu; Jia Sha; Zhonghao Zhu; Kaijun Xiao; Sijian Zhou; Jian Wei (Food Research International, 2026)

A nanoengineered Au@Ag@PVP SERS solid-phase substrate empowered by machine learning for rapid and trace-level screening of pesticide residues in tea - Xifan Zhan; Xinying Wang; Md Mehedi Hassan; Fangling Jiang; Jiaying Xu; Yuan Zhang; Shanghua Li; Sha Zou; Hongfa Liu; Yi Xu; Quansheng Chen (Food Bioscience, 2026)

Enhance glioma treatment by bioinspired nanoplatform loaded with immunostimulants via regulation of glioma immune microenvironment - Linfeng Liu; Wei Lv; Yue Gong; Zhenwei Ding; Kefan Song; Wei Zhao; Hongli Liu; Shengnan Li; Weichong He; Jiaqing Yin; Jiangna Xu; Yuqin Chen; et al. (Chemical Engineering Journal, 2026)

Early Biological Orchestration in Fracture Healing: Decoding the Crosstalk between Inflammation, Coagulation, and Metabolism - Linyuan Xue; Jiyixuan Li; Minglu Hao; Sha Zhou; Ying Yang; Ting Liu; Lei Zhang; Bing Liang; Yingze Zhang; Dongming Xing (Stem Cell Reviews and Reports, 2026)

A modelling study of orbital-scale precipitation variability and oxygen isotope evolution over arid Central Asia - Jing Lei; Zhengguo Shi; Heng Liu; Yingying Sha; Xinzhou Li (Science China Earth Sciences, 2026)

Probiotics as a Therapeutic Strategy for Obesity: New Thoughts on the Stress Response Mechanisms of Probiotics In Vitro and In Vivo - Dingkang Wang; Chao Li; Jingru Ma; Ruijie Xu; Wei Jing; Sha Liu; Xiaomin Sun; Lin Shi; Youfa Wang (Probiotics and Antimicrobial Proteins, 2026)

Melatonin attenuates chronic obstructive pulmonary disease by suppressing NLRP3-mediated pyroptosis in alveolar macrophages - Xiaofeng Li; Zhe Wang; Meng Shi; Tingting Zhang; Sha Huang; Xiaoju Liu (Tissue and Cell, 2026)

Biogas upgrading via microbial electrolysis cell-integrated anaerobic digestion: A critical review of stabilization strategies towards practical application - Sha Tan; Lei Li; Shuang Liu; Linpei Han; Chaoran Duan; Yongli Liu; Xiaoming Wang (Journal of Environmental Management, 2026)

Multi-objective optimization of rice production and environmental sustainability under climate change in the Yangtze River Delta: A DNDC-random forest framework approach - Shuoshuo Liang; Ping He; Qingnan Chu; Wentian He; Ruochen Li; Xinpeng Xu; Rong Jiang; Shuang Liu; Linkui Cao; Zhimin Sha (Field Crops Research, 2026)

Histone H3K27 acetylation of slc25a4 mediates triclocarban-induced transgenerational developmental toxicity in zebrafish (Danio rerio) at subthreshold exposure - Yiming Chang; Zijian Su; Xinyi Jiang; Sihan Huang; Jialing Yu; Zhanyou Li; Keke Liu; Zhijian Sha; Lu Yang; Xiaojia Chen; An hong; Yibo Zhang; et al. (Environmental Research, 2026)

Self-adhesive conductive hydrogel electronic skin for self-powered electrical stimulation to enhance antibacterial activity and accelerate wound healing - Yuxiu Liu; Kun Wang; Rongchen Xu; Yaqi Wang; Changzhen Xu; Yanghui Chen; Bingqi Zhao; Jianan Niu; Wei Sha; Jiangwen Wang; Xue Bai; Hongbo Li; et al. (Chemical Engineering Journal, 2026)

A Multi-omics Atlas of Gonadal Sex Differences and Characterization of the dmrt1 Gene in Gymnocypris Eckloni Herzenstein - Luo Lei; Yinhua Zhou; Qing Liu; Hejiao Li; Wuga Sha; Chaoyang Li; Suxing Fu; Yuting Duan; Rongrong Liao; Can Liu; Dapeng Gu; Linzhen Li; et al. (Marine Biotechnology, 2026)

Coverage path planning for a bagging robot via spatial coordinate projection clustering of young peaches - Hongli Zhang; Jingjian Li; Fenghua Huang; Shulin Liu; Sha Wei; Haihua Xiao; Feng Ding (Computers and Electronics in Agriculture, 2026)

Effects of microplastic contamination on soil nitrogen and its bioavailability in soybean-maize rotation system - Xinkai Jia; Haoqing Li; Darrell W.S. Tang; Sha Xue; Enke Liu; Xiaomei Yang (Soil and Tillage Research, 2026)

Genome-wide identification of the laccase gene family in wheat (Triticum aestivum L.) during Fusarium pseudograminearum infection - Li-Yu Chen; Yi Diao; Ju-Hong Ma; Xiang-Xue Zhang; Rui Li; Yan Liu; Hong-Tao Tang; Zhi Wang; Sha Gao; Rui-Huan Xu; Zhen-sheng Kang; De-Jun Han; et al. (Plant Science, 2026)

A comparative analysis of the properties of doughs prepared by liquid and firm fermentation with a co-culture of Acetobacter tropicalis A3 and Saccharomyces cerevisiae Y10 - Yanxing Wei; Yan Liu; Zongwu Zhang; Huiying Sha; Haifeng Li; Zhijian Li (Journal of Cereal Science, 2026)

Synergistic stabilization of O/W/O double emulsions: Role of gelatin and beeswax-soybean oil in enhancing structural integrity and rheological properties - Sha Ao; Le Li; Yan Li; Bin Li; Shilin Liu (Food Hydrocolloids, 2026)

Double sulfuration promotes the activation of peroxydisulfate by Fe-based N/S co-doped biochar composites to degrade sulfapyridine: Synergistic effect and degradation mechanism - Haozhe Li; Yufeng Sun; Zongtang Liu; Yudong Chen; Zhenghao Fei; Xiankun Wu; Xinlong Sha; Xiaoju Wen; Qirui Guo; Qihui Xu; Yujin Liu; Binbin Qian (Environmental Research, 2026)

Associations of maternal exposure to nonylphenol and bisphenols with precocious puberty in girls: A nested case-control study - Miaomiao Yan; Yanjian Wan; Ruijia Li; Jiahao Li; Xiaoyuan Qin; Yuanyuan Li; Hongxiu Liu; Shunqing Xu; Qianru Zhou; Sha Huang; Wei Xia (Environmental Research, 2026)

Intranasal biomimetic vesicle platform reprograms the glioblastoma microenvironment for enhanced immunotherapy - Shuo Li; Chao Qin; Fan-Yu Qian; Jin-Hao Wang; Xiang-Gui Wu; Wen-Qing Li; Tai-Yu Liu; Zhao-Jie Chen; Bei-Yuan Zhang; Qi-Yue Liu; Li-Sha Liu; Li-Fang Yin (Chemical Engineering Journal, 2026)

Sulfonic acid electrolyte additives realizing high-energy-density magnesium-air batteries by pH-controlled interphase engineering and in situ protective layer construction - Wang Qiang; Sha Jianchun; Li Xue; Chen Weilong; Wang Kehao; Zhang Yusong; Yang Yiqiang; Qiao Mingliang; Tian Jie; Liu Wenhong; Zhao Zhong; Zhang Zhiqiang (Chemical Engineering Journal, 2026)

Types and addition sequences of low molecular organic acids impact the remediation efficiency of cadmium-contaminated soil by biochar - Yunfeng Gao; Yang Jiang; Meiqi Chu; Xu Zhang; Yue Jiang; Jiaqi Zhang; Wei Wang; Xuesheng Liu; Sha Li; Juanjuan Qu; Hongyu Ren (Journal of Soils and Sediments, 2026)

Two new compounds isolated from a sponge-derived fungus Diaporthe sp. ZYX-Z-582 - Jia-Le Chang; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Hai-Tao Li; Jiao-Cen Guo; Hao-Fu Dai; Sha-Sha Liu; You-Xing Zhao (Phytochemistry Letters, 2026)

Material source and genesis analysis of lithium-rich claystone in Balun Mahai Salt Lake, Qaidam Basin - Fan Zhang; Xiwei Qin; Yuliang Ma; Sha Yang; Tong Pan; Jianzhou Chen; Chenglin Liu; Chengwang Ding; Ziwen Jiang; Dong Zhang; Qingkuan Li; Genhou Wang; et al. (Journal of Geochemical Exploration, 2026)

Sustainable lightweight composite nanofibers: efficient control of electromagnetic pollution - Miao Li; Mengxiang Liu; Zihan Kong; Qiong Wu; Yuqi Liu; Sha Han; Tao Zhang; Xiaoxiao Huang (Journal of Cleaner Production, 2026)

Unveiling Cl-induced electrocatalytic Cα-Cβ cleavage mechanism by 1D/2D/1D TiO2@ZIS-Sv@C heterojunction for efficient aromatic aldehyde generation - Jifang Zhang; Chengcheng Suo; Hongru Zhang; Wei Li; Sha Luo; Bing Tian; Chunhui Ma; Shouxin Liu (Journal of Environmental Chemical Engineering, 2026)

Numerical investigation on the influence of temperature on combustion and emission characteristics of NH3/H2/CH4 mixtures under gas turbine conditions - Yanfei Zhang; Qing Hao; Mingming Huang; Zhenxian Liu; Qin Li; Zewen Yu; Jianfang Du; Xiao Zhang; Zhuoming Xiong; Qingkui Zhang; Yumeng Cao; Haoxi Sha (Fuel, 2026)

Regulating the structure of soybean protein isolate-dextran maillard conjugate through cold plasma treatment: enhancing the storage and processing stability of oil-in-water emulsion loaded with curcumin - Liming Tan; Kun Sha; Xin Jia; Lijun Yin; Lizhen Li; Haijie Liu (Food Research International, 2026)

Multifunctional aerogel with antibacterial/photothermal properties for uranium extraction from natural seawater - Zewei Hou; Zhixue Cao; Chaoxu Shen; Guoliang Nie; Zhong Liu; Jianang Sha; Peipei Yang; Songwei Li; Chuntai Liu (Desalination, 2026)

Covalently grafted pyrenoviologen on nano-SiO2 for ultrasensitive fluorescent detection of picric acid - Yiting Wang; Ni Yan; Yawen Li; Jiayao Sha; Yao Liu; Tianle Cao; Tianyue Yuan; Wenjie Ni; Weiqiao Wang; Jiuxu Fu; Gang He (Chemical Engineering Journal, 2026)

GHG emission and reduction of crop residue biochar-based products in different soils: insights from prospective life cycle assessment - Yinan Liu; Yaxi Fang; Hanbing Li; Sumei Li; Sha Chen; Yu Li; Peize Wu (ENGINEERING Environment, 2026)

Progressive Failure Characteristics and Damage Evolution of Anisotropic Rocks with Oriented Arrangement of Minerals Under Triaxial Cyclic Loading and Unloading - Dahai Wang; Changqing Liu; Han Bao; Hengxing Lan; Peng Sha; Bo Li; Shijie Liu; Changgen Yan (Rock Mechanics and Rock Engineering, 2026)

Distribution and potential risks of antibiotics in inland lakes in China - Kejian Chu; Shuo Qin; Zonghao Tian; Fuzhu Ye; Xuan Yang; Li Gu; Yuanyuan Liu; Yang Zhang; Yuanyuan Sha (Environmental Research, 2026)

Amplifying 2′3′-cGAMP with “open source throttling” strategy: Intelligent nanoreactors enhance immunotherapy in HNSCC via cascade activation of the cGAS-STING pathway - Tong Sha; Ze Wang; Jinwei Li; Yahong Wu; Xiaoyi Yu; Jinbiao Qiang; Annan Liu; Hao Liang; Zunxuan Xie; Yijun Zhou; Hongchen Sun; Andrew K. Whittaker; et al. (Chemical Engineering Journal, 2026)

Ti3C2-Cl-Bi12O17Cl2/Bi12O17Cl2 Mott-Schottky heterojunction with mixed noncovalent/covalent type to boost ultra-sensitive photoelectrochemical sensing of ciprofloxacin - Chu-Chu Hu; Qi-E Zhang; Shao-Peng Shi; Guo-Qing Zhao; Yan-Sha Gao; Ping Liu; Xun-Kuan Ye; Yan Pan; Hui-Qing Lv; Li-Min Lu (Chemical Engineering Journal, 2026)

Cellulose based hierarchical structural colored wood composite material for daytime radiative cooling - Biyao Sun; Shaoyi Cao; Shuliang Dou; Yudong Li; Wenye Sun; Chunhui Ma; Sha Luo; Mingcong Xu; Shouxin Liu; Wei Li (Carbohydrate Polymers, 2026)

Analysis of odor and VOCs pollution in industrial parks of central inner Mongolia autonomous region based on mobile monitoring - Chaofei Li; Yuanhao Jia; Yu Qiu; Cheryl Marie Cordeiro; Sha Li; Yanying Chen; Jinxing Liu; Heinz W. Siesler; Hongkan Wu; Run Zhao (Atmospheric Environment, 2026)

Comparison of environmental impact mitigated for Fe3O4-based nano-detergents: A life cycle perspective & scenario analysis - Xiaotong Li; Mengrong Zhang; Hanbing Li; Sha Chen; Sumei Li; Jingfu Liu (Sustainable Production and Consumption, 2025)

Straw return impacts on crop yield and yield variability: A meta-analysis - Kexin He; Bao-Luo Ma; Xiaofei Wei; Sha Guo; Chengcheng Feng; Chenyang Liu; Yongqing Ma; Pufang Li (Soil and Tillage Research, 2025)

Postharvest application of plasma-activated water delays anthracnose symptom development in apples - Yingman Gao; Ruichen Sha; Guihuan Wei; Lingling Yang; Yupan Zhu; Yudong Liu; Ruonan Ma; Zhen Jiao; Bing Li (Postharvest Biology and Technology, 2025)

Efficient HCHO oxidation via reaction and diffusion intensification on TOCNFs@MnOx - Ke Cheng; Xue Liu; Sha Luo; Ruiwen Wang; Chunhui Ma; Bing Tian; Wei Li; Shouxin Liu (Journal of Environmental Chemical Engineering, 2025)

A molecular imprinting-switchable laccase-like nanozyme-based onsite self-calibrating assay of ethyl carbamate residues - Heng Wang; Cancan Jia; Siyu Huang; Sha Li; Xin Liu; Wenjuan Chen; Yizhong Shen (Food Chemistry, 2025)

Synergistic co-encapsulation of Saccharomyces cerevisiae and Lactobacillus helveticus in water-in-water Pickering emulsion with enhanced probiotic viability and digestive resistance - Yajie Li; Jie Zhang; Sha Ao; Huaqiang Cao; Yan Li; Bin Li; Shilin Liu (Food Bioscience, 2025)

Emission characteristics of full-volatility organic compounds from China's aluminum-products industry and their impacts on secondary organic aerosol and ozone potentials - Dongyang Wu; Qing'e Sha; Shan Jiang; Luyun Liu; Citao Zhang; Jialin Song; Junhao Xu; Haoqi Chen; Guanghui Li; Zhangmin Xiang; Bin Jiang; Zhuangmin Zhong; et al. (Environmental Research, 2025)

Structure-optical activity relationship of chiral helical gold nanorods and their application in alkaline phosphatase detection - Shuai Wen; He Feng Shi; Can Nan Zhao; Ying Ying Xiong; Liang Tong Li; Qiu Yue Liu; Chen Liu; Qiu Sha Li; Wei Wang; Jian Wang (Chemical Engineering Journal, 2025)

Deep eutectic solvent driven hydrogen bond confinement synthesis of multifunctional carbon dots from Licorice residues - Wenbo Cui; Xin Zhao; Jiali Song; Jianwei Zhao; Chunfa Zhang; Chunhui Ma; Mingcong Xu; Ruiwen Wang; Sha Luo; Shouxin Liu; Wei Li (Chemical Engineering Journal, 2025)

Fracture Characteristics and Quantitative Analysis of Anisotropic Rock with Direction-Arranged Minerals Subjected to Triaxial Cyclic Loading: A Case of Biotite Quartz Schist - Han Bao; Yankai Wang; Changqing Liu; Qun Qi; Hengxing Lan; Shengwen Qi; Bo Li; Peng Sha; Hongtao Lv (Rock Mechanics and Rock Engineering, 2025)

Prevalence and spectrum of STRC variants in 1015 sensorineural hearing loss patients: insights from the Chinese population - Luo Guo; Sha Yu; Wenrui Zhao; Liheng Chen; Guiqing Cheng; Weitao Li; Wei Li; Haiting Ji; Shan Sun; Huiqian Yu; Haiying Liu; Chunyi Gui; et al. (Molecular Genetics and Genomics, 2025)

IFNGR1, IRF8 genetic polymorphisms modulate the susceptibility of non-tuberculous mycobacteria pulmonary disease and influence the patients’ treatment outcomes and immune status - Li-ping Cheng; Zhi-bin Liu; Lei Wang; Jie Cao; Qing-rong Qu; Hai Lou; Xiao-na Shen; Juan Yang; Yuanyuan Yu; Rui Juan Zheng; Wei Sha; Qin Sun (Inflammation Research, 2025)

Transcriptome analysis reveals no obvious unintended effects in the spleen of CRISPR/Cas9-mediated CD163 and pAPN double-knockout pigs - Zhi-Guo Liu; Nan Wang; Wan-Jie Wang; Lei Huang; Shun-Shun Chi; Yu-Xin Nie; Mao-Sha Yuan; Ya-Ru Sun; Yu-Lian Mu; Kui Li (Functional & Integrative Genomics, 2025)

Plant–soil feedback alters plant–soil–microbial nutrient status and elemental-limitation status during secondary succession - Yong Cao; Zemin Ai; Xinghua Li; Mengjia Hou; Yuyan Yao; Yi Deng; Huan Liu; Jiaoyang Zhang; Guobin Liu; Sha Xue (Soil Ecology Letters, 2025)

Chronic dietary exposure to BDE-47 can induce inflammatory responses in the brain of common carp (Cyprinus carpio) and further trigger neurotoxicity through the 5-HT pathway - Huimin Sun; Youlian Liu; Yujie Huang; Mengbin Yuan; Zujun Ye; Rong Yang; Fuqiang Sha; Ni Tang; Bo Zhou; Defang Chen; Zhiqiong Li; Xin Zhang (Science of The Total Environment, 2025)

The protein kinase MLOP1 mediates pectin fragment signaling and feedback regulation of cell wall synthesis - Xiaohui Liu; Jingjing Sha; Qingyao Li; Shuai Yuan; Jialin Tao; Shihan Fu; Pu Gan; Qiuyan Lan; Johannes Liesche; Chaowen Xiao (Journal of Plant Physiology, 2025)

Carbohydrate-metabolizing gastrointestinal bacteria mediate resistome divergence in high feed efficiency Holstein dairy calves - Tianyu Chen; Shangru Li; Jianxin Xiao; Rong Peng; Mo Sha; Jingjun Wang; Jiaying Ma; Wei Wang; Mei Ma; Shengli Li; Zhijun Cao; Shuai Liu (Journal of Hazardous Materials, 2025)

Oxidative potential of atmospheric aerosols: Research progress on pollution characteristics and mechanism - Bo Wang; Qingcai Chen; Tong Sha; Xin Zhu; Huan Liu; Qingwen Wang; Yang Li (Environmental Pollution, 2025)

Biocompatible chitosan-assisted green-synthesized AgNPs-PSPAE nanoplatform for synergistic antimicrobial and anti-inflammatory therapy in infected wound healing - Yuxin You; Jiamin Li; Fructueux Modeste Amona; Luyuan Yang; Yijia Yang; Xinyi Liu; Chengbin Shi; Ziqi Sha; Yanzhu Li; Fangxu Bu; Lixuan Cao; Yuxi Zhou; et al. (Chemical Engineering Journal, 2025)

Involvement of ductal reaction in Di-(2-ethylhexyl)-phthalate-caused hepatic fibrosis: Molecular mechanisms and potential intervention strategies - Xinru Du; Shu Zhang; Sha Liu; Yancheng Gao; Zhendong Wang; Na Dong; Sisi Song; Qinming Hui; Ziyi Wang; Yue Ma; Chunxiao Zhou; Ye Yang; et al. (Chemico-Biological Interactions, 2025)

Incremental learning-enhanced ensemble surrogate-assisted evolutionary algorithm for lifelong berth allocation and quay crane assignment problems - Li-Sha Xu; Yi-Ming Wang; Ting Huang; Yue-Jiao Gong; Jing Liu (Swarm and Evolutionary Computation, 2025)

Hydrofluoric-acid-mediated hydrothermal synthesis of anatase TiO2 with {101}/{001} facets for selective photocatalytic valorization of glycerol to syngas - Zheng Yang; Haoqiang Hou; Ermiao Liang; Kun Zhang; Mingcong Xu; Chunhui Ma; Wei Li; Sha Luo; Shouxin Liu (Journal of Environmental Chemical Engineering, 2025)

Catalyzation of chlorine dioxide by manganese dioxide for efficient PAHs removal in industrial soil: New insight from relative reactive oxygen species generation - Xiaojun Hu; Qiying Li; Xuhan Lin; Bo Cheng; Zhiwen Cheng; Xuehong Yuan; Jinju Hou; Cheng Shen; Chenyan Sha; Fuwen Liu (Journal of Environmental Chemical Engineering, 2025)

Photocatalytic biorefining green closed-loop: Photocatalytic alkali lignin depolymerization in supramolecular solvent - Chengcheng Suo; Xiaochang Zhang; Xinai Li; Jifang Zhang; Hongru Zhang; Rui Teng; Wei Li; Sha Luo; Bing Tian; Qingjiang Pan; Chunhui Ma; Zhijun Chen; et al. (Journal of Environmental Chemical Engineering, 2025)

Network pharmacology and molecular docking reveal the potential mechanisms of edible Fritillariae cirrhosae bulbus in alleviating asthma-related symptoms: A transcriptomics-supported study - Lingyi Liu; Ruisi Zhu; Yuzhi Luo; Lingli Li; Sha Wen; Songyuan Xia; Yajing Ma; Huixin Song; Weifeng Li; Xiaofeng Niu (Food Bioscience, 2025)

The effect of uracil on the freeze-drying survival rate of Lactiplantibacillus plantarum YR07 based on transcriptome analysis - Sha-sha Zheng; Wen-di Zhang; Li-jun Tan; Li-fang Zou; Ying-ying Hu; Liu Yang; Bao-cai Xu (Food Microbiology, 2025)

Genome-wide characterization and immune-modulatory roles of PPAR genes in Cynoglossus semilaevis: insights into inflammation regulation and host defense - Yishuai Li; Mengyang Chang; Suxu Tan; Wenwen Wang; Kunpeng Shi; Shaoqing Zang; Zhujun Li; Jin Liu; Zhenxia Sha (Fish & Shellfish Immunology, 2025)

Rice-duck farming enhances phosphorus use and grain yield via altering soil phosphorus fractions in the Yangtze River Delta of eastern China - Hui Gao; Qingnan Chu; Xiangyu Liu; Liang Zheng; Shuhan Xu; Linkui Cao; Detian Li; Shuai Yin; Ping He; Chengrong Chen; Zhimin Sha (Agriculture, Ecosystems & Environment, 2025)

Cellulose-based biomass foams for food packaging: current trends and future challenges - Huaqiang Cao; Xiaoqi Ding; Sha Ao; Weizhi Huang; Shaojun Wang; Feng Li; Le Li; Yan Li; Bin Li; Qi Li; Shilin Liu (Trends in Food Science & Technology, 2025)

Insights into solidification mechanism of Cr(III) and Cr(VI) in chromite ore processing residue via composite geopolymers synthesized from calcined red mud and granulated blast furnace slag - Yan Ke; Sha Liang; Huabo Duan; Junda Quan; Xingwu Li; Huijie Hou; Jingping Hu; Yin Yang; Xing Liu; Yibing Zuo; Jiakuan Yang (Journal of Hazardous Materials, 2025)

Protective effects of rosmarinic acid against oxidative damage and atherosclerosis via the PI3K/AKT pathway - Tiantian Tang; Mingze Sun; Baiyuan Sha; Rui Liu; Zhiyang Ren; Liwei Li; Ye Zhang; Hao Wang; Kai Yu (Food and Chemical Toxicology, 2025)

Glycine-mediated hydrogen bond network reconstruction and interfacial engineering for ultrahigh-voltage aqueous magnesium air batteries - Sha Jianchun; Liu Zhoulin; Wang Qiang; Li Xue; Yang Yiqiang; Tian Jie; Chen Weilong; Liu Wenhong; Wu Liang; Zhang Zhiqiang (Chemical Engineering Journal, 2025)

Coupling covalent organic framework with polyacrylamide to construct a robust composite hydrogel electrolyte for dendrite-free and long-lifespan aqueous zinc-ion batteries - Ziming Liu; Xiangcai Li; Heng Zhang; Xuke Zhang; Junyuan Li; Yifei Shi; Dongxiang Geng; Zhaolei Li; Dawei Sha; Genxi Yu; Chao Yan (Chemical Engineering Journal, 2025)

Microbiome catalog and dynamics of the Chinese liquor fermentation process - Xue Zhu; Liangqiang Chen; Pengshuo Yang; Sha Luo; Mengjing Teng; Wenjie Zhu; Yuxue Li; Dan Zhao; Nan Wang; Xiaoke Chen; Mingyue Cheng; Huabin Tu; et al. (Bioresource Technology, 2025)

Identification of an adaptor protein 2σ gene for OsTGW12 to determine grain weight and potentiate quality breeding in rice - Xiaoqiong Li; Huangai Li; Ke Xie; Jinling Han; Kaiqiang Liu; Ying Chen; Jingang Qi; Hongpei Jin; Hanhua Tong; Aihua Sha; Sibin Guo (Theoretical and Applied Genetics, 2025)

Straw return significantly enhances wheat yield in higher precipitation environment by promoting larger root diameters, wider xylem channels, and thinner root cortex - Xiaofei Wei; Kexin He; Bao-Luo Ma; Sha Guo; Chengcheng Feng; Chenyang Liu; Yongqing Ma; Pufang Li (Plant and Soil, 2025)

7-Hydroxylathyrol defeats geminivirus through targeting C4 and activating host defense - Bi Wang; Xiaoxiao Xu; Wenhao Liang; Tong Shi; Qizhi Wang; Yu Chen; Sha Chen; Fei Liu; Linwei Li (Pesticide Biochemistry and Physiology, 2025)

Hydroxyl-tunable type I photosensitizer based on curcumin for photodynamic therapy against hypoxic tumor cells - Yanping Wang; Tong Mu; Xuewei Li; Xiuli Zheng; Jie Sha; Zhe Yu; Yuanyuan Qin; Haohui Ren; Ying Wang; Weimin Liu; Pengfei Wang (Journal of Photochemistry and Photobiology B: Biology, 2025)

Sustainable remediation of butyl xanthate-contaminated mine wastewater by combining emergent macrophyte Cyperus alternifolius with a versatile bacterial isolate - Qi Liu; Yao-Yao Ye; Sha Yang; Cheng-Yu Cui; Huan Du; Jin-Cheng Ye; Ji-Liang Cheng; Rui-Wen Hu; Lei Xiang; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; et al. (Journal of Hazardous Materials, 2025)

Unveiling interactions between anammox and denitrification from long-term steady-state scale and transient kinetic scale in a granular sludge system - Hao Tan; Fengjun Yin; Jinjin Zheng; Xuehai Yue; Ying Zhao; Sha Wang; Cheng Song; Yongzhi Li; Hong Liu (Bioresource Technology, 2025)

Hepatotoxic effects of exposure to different concentrations of Dibutyl phthalate (DBP) in Schizothorax prenanti: Insights from a multi-omics analysis - Luo Lei; Wuga Sha; Qing Liu; Shidong Liu; Yinhua Zhou; Rundong Li; Yuting Duan; Suxing Fu; Hejiao Li; Rongrong Liao; Linzhen Li; Rongzhu Zhou; et al. (Aquatic Toxicology, 2025)

NPK-N application limits grain cadmium concentration of wheat via promoting Cd export during grain filling - Yiran Cheng; Yuanjiang He; Jia Chen; Weiping Li; Wenhui Xiang; Xing Chen; Dan Long; Jian Zeng; Yang Liu; Dongwei Wang; Dandan Wu; Lina Sha; et al. (Plant and Soil, 2025)

Identification and Characterization of LBD Gene Family in Pseudoroegneria libanotica Reveals Functions of PseLBD1 and PseLBD12 in Response to Abiotic Stress - Xunzhe Yang; Xiang Li; Xia Wang; Chen Chen; Dandan Wu; Yiran Cheng; Yi Wang; Lina Sha; Houyang Kang; Songqing Liu; Xing Fan; Yinglong Chen; et al. (Biochemical Genetics, 2025)

Root hair: An important guest-meeting avenue for rhizobia in legume–Rhizobium symbiosis - Jingwen Xiao; Wenxu Liu; Bicong Wu; Yuling Zhang; Sha Li; En Li (Plant Science, 2025)

A simplified conservation flux scheme for gas kinetics based on OpenFOAM framework I: Shakhov model - Mengbo Zhu; Jianfeng Chen; Xiaoqiang Li; Congshan Zhuo; Sha Liu; Chengwen Zhong (Computer Physics Communications, 2025)

Electrochemical nitrite sensing using mass transfer signal with a catalyst-free small-sized rotating disk electrode for wastewater monitoring - Fengjun Yin; Xiaohui Yang; Shun Lu; Hanlin Zhang; Ying Zhao; Sha Wang; Cheng Song; Yongzhi Li; Zhaoming Chen; Hong Liu (Water Research, 2025)

Development and Optimization of an Integrated Disk-Blade Silage Device for Efficient Cane Top Collection and Processing - Peng Huo; Shaochun Ma; Baocheng Zhou; Wenzhi Li; Changyu Wang; Wei Liu; Sha Yang; Junhua Liu (Sugar Tech, 2025)

Correction: Discovery of novel 4-trifluoromethyl-2-anilinoquinoline derivatives as potential anti-cancer agents targeting SGK1 - Guangcan Xu; Lanlan Li; Mengfan Lv; Cheng Li; Jia Yu; Xiaoping Zeng; Xueling Meng; Gang Yu; Kun Liu; Sha Cheng; Heng Luo; Bixue Xu (Molecular Diversity, 2025)

Discovery of novel 4-trifluoromethyl-2-anilinoquinoline derivatives as potential anti-cancer agents targeting SGK1 - Guangcan Xu; Lanlan Li; Mengfan Lv; Cheng Li; Jia Yu; Xiaoping Zeng; Xueling Meng; Gang Yu; Kun Liu; Sha Cheng; Heng Luo; Bixue Xu (Molecular Diversity, 2025)

Agricultural practices influence phosphorus transport and ecosystem health in rice-paddy systems: Insights from HYDRUS-1D simulations - Shuoshuo Liang; Qingnan Chu; Ali Ashrafi; Zheng Zhao; Xiangyu Liu; Shuang Liu; Bei Yang; Detian Li; Ping He; Linkui Cao; Zhimin Sha; Chengrong Chen (Agriculture, Ecosystems & Environment, 2025)

Multiple stimuli-responsive circularly polarized luminescent bio-composite films by coassembling cellulose nanocrystals and curcumin - Shaoyi Cao; Jingpeng Wang; Wenye Sun; Bang An; Mingcong Xu; Sha Luo; Chunhui Ma; Haipeng Yu; Zhijun Chen; Jian Li; Wei Li; Shouxin Liu (Carbohydrate Polymers, 2025)

Urban form regulation for synergetic PM2.5 and O3 control: A multi-indicator constrained DNN simulation - Sha Li; Bin Zou; Ning Liu; Weiwen He; Shenxin Li; Xuying Ma (Science of The Total Environment, 2025)

Paleoceanographic evolution of the Chukchi Sea over the past 7600 years inferred from diatom assemblages - Tong Li; Yanguang Liu; Longbin Sha; Tengfei Song; Xinyi Wang; Bin Wu; Jianghu Lan; Dongling Li (Marine Geology, 2025)

Modification of electrochemical and discharge performance of extruded Mg-3Sn-1Ca as anode for magnesium-air batteries with solid solution element Zn and Zr - Jiaxin Bao; Yusong Zhang; Lianhui Li; Jianchun Sha; Jie Tian; Xue Li; Yiqiang Yang; Wenhong Liu; Zhiqiang Zhang (Chemical Engineering Journal, 2025)

Advancements in machine learning for spatiotemporal urban on-road traffic-air quality study: A review - Zhanxia Du; Hanbing Li; Sha Chen; Xinming Zhang; Lantian Zhang; Yuting Liu (Atmospheric Environment, 2025)

Combined skin injury model from airblast overpressure and seawater immersion in rats: establishment, characterization, and mechanistic insights - Jinpeng Du; Zhao Li; Yi Kong; Wei Song; Zhongming Chen; Mengde Zhang; Yuyan Huang; Chao Zhang; Xu Guo; Linhao Hou; Yaxin Tan; Liting Liang; et al. (Journal of Molecular Histology, 2025)

Increase of ATP synthesis and amino acids absorption contributes to cold adaptation in Antarctic bacterium Poseidonibacter antarcticus SM1702T - Wen-Yue Xu; Sha-Sha Liu; Xiao-Han Guo; Peng Wang; Chun-Yang Li; Li Liao; Qi-Long Qin (Extremophiles, 2025)

Development and verification of the multi-group covariance processing code CovarXS - Sha LIU; Xubo MA; Songyi Li (Annals of Nuclear Energy, 2025)

Advanced design of the crushing chamber for the sugarcane top silage cutter in harvester with experiments and simulation - Peng Huo; Shaochun Ma; Jun Qian; Weiqing Li; Baocheng Zhou; Wei Liu; Wenpeng Liang; Wenzhi Li; Changyu Wang; Sha Yang; Lingfeng Li; Yechen Li; et al. (Computers and Electronics in Agriculture, 2025)

Cavity as radio telescope for galactic dark photon - Yanjie Zeng; Yuxin Liu; Chunlong Li; Yuxiang Liu; Bo Wang; Zhenxing Tang; Yuting Yang; Liwen Feng; Peng Sha; Zhenghui Mi; Weimin Pan; Tianzong Zhang; et al. (Science Bulletin, 2025)

FOXD1 activates KIFC1 to modulate aerobic glycolysis and reinforce cisplatin resistance of breast cancer - Haitao Gao; Jing Wang; Jiacai Liu; Huihua Wang; Tiantian Wang; Sha Li; Lili Niu; Ya Wei (Reproductive Biology, 2025)

Sulfur dioxide increases testosterone biosynthesis by activating ERK1/2 pathway and disrupting autophagy in Leydig cells - Xiang Li; Yan Shi; Sha Liu; Zhiyuan Feng; Haoran Xiao; Rui Li; Zirou Li; Xinyue Zhang; Yongli Han; Jundong Wang; Chen Liang; Jian Bai; et al. (Journal of Hazardous Materials, 2025)

Identifying spatial drivers of soil heavy metal pollution risk integrating positive matrix factorization, machine learning, and multi-scale geographically weighted regression - Yujie Pan; Anmeng Sha; Wenjing Han; Chang Liu; Guowangchen Liu; Emily Welsch; Min Zeng; Shasha Xu; Yi Zhao; Shang Tian; Yiyi Li; Rui Deng; et al. (Journal of Hazardous Materials, 2025)

A novel framework for river organic carbon retrieval through satellite data and machine learning - Shang Tian; Anmeng Sha; Yingzhong Luo; Yutian Ke; Robert Spencer; Xie Hu; Munan Ning; Yi Zhao; Rui Deng; Yang Gao; Yong Liu; Dongfeng Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Forest thinning effects on soil carbon stocks and dynamics: Perspective of soil organic carbon sequestration rates - Qing Qu; Hongwei Xu; Lin Xu; Chengming You; Bo Tan; Han Li; Li Zhang; Lixia Wang; Sining Liu; Zhenfeng Xu; Sha Xue; Minggang Wang (CATENA, 2025)

Multi-organ toxicity caused by PM2.5 in mice with cardiovascular diseases: The role of PAHs played from the most polluted episodes in China - Jinjin Yu; Jian Sun; Yajing Ma; Xinyi Niu; Ruisi Zhu; Huixin Song; Lingyi Liu; Yuzhi Luo; Songyuan Xia; Jingyu Wang; Lingli Li; Sha Wen; et al. (Journal of Environmental Management, 2025)

Biomonitoring and food surveillance on heavy metals reveal need for food safety in a coastal region - Xin Zhang; Xiaoqian Yang; Xiaoyue Hu; Zhonghua Meng; Zhigang Yu; Zhan Sun; Ying Zhang; Zhifeng Yang; Sha Li; Jia-Sheng Wang; Qiang Jia; Lanzheng Liu; et al. (Food Research International, 2025)

Water-in-water Pickering emulsions as a fascinating culture and embedding medium for Saccharomyces cerevisiae - Sha Ao; Yudong Sun; Xiaoqi Ding; Congying Zhou; Yuan Wang; Junxia He; Huaqiang Cao; Yan Li; Bin Li; Shilin Liu (Food Bioscience, 2025)

Analysis of growth physiological changes and metabolome of highland barley seedlings under cadmium (II) stress - Yingyong Luo; Xian Huang; Ajia Sha; Jing He; Xiaodie Chen; Wenqi Xiao; Lianxin Peng; Liang Zou; Bingliang Liu; Qiang Li (Environmental Pollution, 2025)

Creating rich closed nanopores in anthracite-derived soft carbon enables greatly-enhanced sodium-ion storage in the low-working-voltage region - Jiawei Gu; Yiwei You; Miao Liu; Ling Huang; Zhefei Sun; Junjie Liu; Liyuan Sha; Minghui Chen; Sha Li; Shunqing Wu; Qiaobao Zhang; Li Zhang (Chemical Engineering Journal, 2025)

Design and synthesis of N-aryl-2-trifluoromethyl-quinazoline-4-amine derivatives as potential Werner-dependent antiproliferative agents - Huimin Li; Jia Yu; Gang Yu; Sha Cheng; Hui Wu; Jiaomei Wei; Chang You; Kun Liu; Menghan Wang; Xueling Meng; Guangcan Xu; Heng Luo; et al. (Molecular Diversity, 2025)

Host selection behavior of Spodoptera exigua (Lepidoptera: Noctuidae, Hübner, 1808) in response to Rosmarinus officinalis (Lamiales: Lamiaceae, Linnaeus, 1753) volatiles - Qiuyu Zhao; Chao Liu; Sha Xie; Guiyan Chen; Xiaoqin Yang; Yanxiang Xu; Fazhong Yang; Yunxian Li (Arthropod-Plant Interactions, 2025)

The autotoxicity of dissolved organic matter from Microcystis may be a contributor to the decline of its bloom - Jun Sha; Lirong Song; Chao Liu; Fang Bai; Haiyang Zhang; Zichao Gong; Tianli Li; Jin Liu; Guangbin Gao; Yunlu Jia (Water Research, 2025)

Recognizing and reconciling dynamic stakeholder conflicts for sustainability in old residential community renovation project strategies - Yue Teng; Yinghui Bao; Yushi Wang; Sha Liu; Zhongfu Li; Robert L.K. Tiong (Environmental Impact Assessment Review, 2025)

Apoc1 Knockdown Alleviates High Glucose-induced Oxidative Stress and Apoptosis of Renal Tubular Cells by Binding to Clusterin - Liyin Chai; Zhengyang Liu; Jun Zeng; Li Gong; Sha Xiang; Jing Yu; Haili Sun; Chaolin Wen; Fang Wang; Ning Li; Bingbing Shen; Mei Mei (Cell Biochemistry and Biophysics, 2024)

Unveiling the susceptibility mechanism of Microcystis to consecutive sub-lethal oxidative stress—Enhancing oxidation technology for cyanobacterial bloom control - Fang Bai; Jie Li; Tianli Li; Jun Sha; Jin Liu; Lin Li; Guofei Dai; Yunlu Jia; Lirong Song (Journal of Hazardous Materials, 2024)

Source-oriented health risk assessment and priority control factor analysis of heavy metals in urban soil of Shanghai - Cheng Shen; Shenfa Huang; Min Wang; Jian Wu; Jinghua Su; Kuangfei Lin; Xiurong Chen; Tianhao He; Ye Li; Chenyan Sha; Min Liu (Journal of Hazardous Materials, 2024)

Predicting green technology innovation in the construction field from a technology convergence perspective: A two-stage predictive approach based on interpretable machine learning - Shuai Feng; Guiwen Liu; Tianlong Shan; Kaijian Li; Sha Lai (Journal of Environmental Management, 2024)

Comparison of Pb adsorption and transformation behavior induced by chicken manure and its DOM in contaminated soil - Yue Jiang; Wei Yang; Jiaqi Zhang; Xuesheng Liu; Yu Jin; Sha Li; Juanjuan Qu; Wei Wang (Journal of Environmental Chemical Engineering, 2024)

1T/2H-MoS2/CdS heterojunction for the co-production of lactic acid photoreforming to hydrogen and value-added chemicals - Ermiao Liang; Xue Liu; Zheng Yang; Jifang Zhang; Yabo Qi; Rui Teng; Wenbo Cui; Mingcong Xu; Sha Luo; Chunhui Ma; Shouxin Liu; Wei Li (Journal of Environmental Chemical Engineering, 2024)

Butterfly wing-inspired superhydrophobic photonic cellulose nanocrystal films for vapor sensors and asymmetric actuators - Bang An; Mingcong Xu; Wenye Sun; Chunhui Ma; Sha Luo; Jian Li; Shouxin Liu; Wei Li (Carbohydrate Polymers, 2024)

A Protocol for Body MRI/CT and Extraction of Imaging-Derived Phenotypes (IDPs) from the China Phenobank Project - Chengyan Wang; Shuo Wang; Sha Hua; Ruokun Li; Yan Li; Zhang Shi; Kai Feng; Lizhen Lan; Meng Liu; Xutong Kuang; Xueqin Xia; Shihai Zhao; et al. (Phenomics, 2024)

Capsaicin combined with stem cells improved mitochondrial dysfunction in PIG3V cells, an immortalized human vitiligo melanocyte cell line, by inhibiting the HSP70/TLR4/mTOR/FAK signaling axis - Yifei Wu; Xiaochuan Wang; Jiayu Zhang; Sha Du; Zhiqiong Wang; Jinrong Li; Wenhe Zhang; Jie Xiang; Renfu Li; Jing Liu; Xin Bi (Molecular Biology Reports, 2024)

The Response of Grassland Production to N and P Fertilizer Management Mediated soil Nematode Community in Qinghai-Tibet Plateau of China - YuanZe Li; HuaKun Zhou; QiFan Zhao; WenJing Chen; HongFei Liu; Bing Yang; Yang Wu; GuoBin Liu; Sha Xue (Journal of Soil Science and Plant Nutrition, 2024)

Identification and bioactivity evaluation of twelve previously undescribed depsidone derivatives from Garcinia oligantha - Xiao-Hui Peng; Sha Chen; Xiao-Fan Liu; Jin-Yuan Yang; Fan-Zhu Meng; Hao Cao; Da-Hong Li; Hui-Ming Hua (Phytochemistry, 2024)

Adverse effect of TWPs on soil fungi and the contribution of benzothiazole rubber additives - Chu Peng; Yuan Wang; Xiaoyu Sha; Mengxi Li; Xinling Wang; Jiao Wang; Yu Wang; Chunguang Liu; Lei Wang (Journal of Hazardous Materials, 2024)

Air quality and health benefits of achieving carbon-neutrality in building sector over Beijing, China - Mengya Wang; Yingying Liu; Sumei Li; Parham Azimi; Sha Chen; Steve Hung Lam Yim (Journal of Environmental Management, 2024)

Occurrence, spatial distribution, and ecological risk of benzotriazole UV stabilizers (BUVs) in sediments from Bohai sea of China - Xing Liu; Xiaodan Pei; JiaoJiao Li; Yawen Wei; Hao Sun; Zilan Wu; Sha Wang; Jianmin Chen; Zhongsheng Lin; Ziwei Yao (Environmental Research, 2024)

An air-rechargeable Zn-organic battery with unprecedented fast self-charging rate - Yiqing Li; Xinin Zhang; Mi Gan; Jiangbo Sha; Yuegang Zhang; Jinzhang Liu (Chemical Engineering Journal, 2024)

Green chemistry closed-loop: Photocatalytic cleavage lignin β-O-4 bond utilizing visible light by Bi2O3/Bi2WO6 in deep eutectic solvent at room temperature - Chengcheng Suo; Jintao Yu; Jifang Zhang; Wei Li; Sha Luo; Chunhui Ma; Shouxin Liu (Biomass and Bioenergy, 2024)

Olink proteomics and lipidomics analysis of serum from patients infected with non-tuberculous mycobacteria and Mycobacterium tuberculosis - Li Wang; Guoling Yang; Liang Guo; Lan Yao; Yidian Liu; Wei Sha (Inflammation Research, 2024)

Inhaled delivery of cetuximab-conjugated immunoliposomes loaded with afatinib: A promising strategy for enhanced non-small cell lung cancer treatment - Sha Liu; Daoyuan Chen; Xiaosu Zhu; Xiaowen Wang; Xiao Li; Yuan Du; Peng Zhang; Jingwei Tian; Yingjian Song (Drug Delivery and Translational Research, 2024)

Construction of 2-azidacetic acid functionalized high-crystallinity fluorescent covalent organic framework: Applications in mitoxantrone and Fe3+ sensing and adsorption - Yuemeng Zou; Famin Ke; Yulian Yang; Dandan Wang; Mingyue Wang; Qiuyi Liu; Sha Yu; Lingling Li; Yue Lan; Xilin Yang; Xiurong Guo; Xiang Li; et al. (Chemosphere, 2024)

Carbon nanomaterials-based smart dual-mode sensors for colorimetric and fluorescence detection of foodborne hazards - Feifei Sun; Peiran Li; Guojian Wu; Fengjiao He; Sha Liu; Yizhong Shen; Yongning Wu; Lin Li (Trends in Food Science & Technology, 2024)

Benzotriazole ultraviolet absorbents in surface waters and sediments of the Bohai Sea and North Yellow Sea: Spatial trends and influencing factors - Xing Liu; Zilan Wu; Xiaodan Pei; Tian Lin; Jiaojiao Li; Sha Wang; Zhigang Guo; Ziwei Yao (Science of The Total Environment, 2024)

An accurate and efficient forecast framework for fine PM2.5 maps using spatiotemporal recurrent neural networks - Ning Liu; Bin Zou; Yi Li; Zengliang Zang; Shan Xu; Sha Li; Shenxin Li; Lu Zhi; Jun Chen; Fang Zhao (Journal of Cleaner Production, 2024)

The resistance mechanism of humic acids and proteins in soluble microbial products from activated sludge against silver nanoparticles - Jia Kang; Yi-hang Wang; Yao-wen Zhang; Chu-qiong Song; Ao-di Wang; Ning Zhou; Yi-hui Zhang; Fa-zhan Li; Shu-li Liu; Li-sha Liu; Gang-fu Song; Bai-hong Wang (Journal of Environmental Chemical Engineering, 2024)

Multilevel regulation of lactose operon in Bacillus licheniformis: Coordination of LacR, CcpA and TnrA regulators - Siyu Li; Fengxu Xiao; Hehe He; Yupeng Zhang; Pengyang Liu; Ying Xu; Lihuang Zhang; Sha Xu; Zhongyang Ding; Guiyang Shi; Youran Li (Food Bioscience, 2024)

Glycoprotein from selenium-enriched yam activates immune cells and enhances intestinal immunity via the NF-κB signaling pathway - Siqi Wang; Jinjin Yu; Lili Zhou; Yuzhi Luo; Lingyi Liu; Sha Wen; Lingli Li; Yajing Ma; Huixin Song; Song Ming; Weifeng Li; Xiaofeng Niu (Food Bioscience, 2024)

Constructing multi-dimensional alternating layer nested structure for enhancing electromagnetic shielding, thermal management and strain sensing - Dingwen Yin; Jinbao Li; Simin Wang; Huijuan Xiu; Gengmei Liu; Shaoyan Huang; Sha Fan; Mengxia Shen; Yanfei Pan (Chemical Engineering Journal, 2024)

Parametric analysis on mechanical performance and additional reinforcement design method of reinforced concrete chimneys with openings - Zhi-Qian Dong; Gang Li; Song-Ke Zhang; Sha-Yi Wang; Ding-Hao Yu; Zeng-Bo Yao; Chun-Gang Liu; Mei Yang (Bulletin of Earthquake Engineering, 2024)

How does intercropping contribute to soil organic carbon accumulation? A global synthesis - Shujuan Li; Sha Ye; Zeqin Liu; Muhammad Umair Hassan; Guoqin Huang; Quan Zhou (Agriculture, Ecosystems & Environment, 2024)

Electrical resistivity structure of the Southeastern part of Bayan Har Block: Insights into the seismogenic environment of 2022 Maerkang earthquake swarm - Yan Zhan; Xiangyu Sun; Xuehua Liu; Lingqiang Zhao; Dahu Li; Sha Li; Zeyi Dong; Xiaoyu Lou; Chongtao Hao; Yuxin Bao (Tectonophysics, 2024)

Multi-omics insights into the function and evolution of sodium benzoate biodegradation pathway in Benzoatithermus flavus gen. nov., sp. nov. from hot spring - Chao-Jian Hu; Yi-Qing Lv; Wen-Dong Xian; Jian-Yu Jiao; Zheng-Han Lian; Sha Tan; Meng-Meng Li; Zhen-Hao Luo; Ze-Tao Liu; Ai-Ping Lv; Lan Liu; Mukhtiar Ali; et al. (Journal of Hazardous Materials, 2024)

Regeneration diagnosis for the service lifespans of residential buildings on a circular economy perspective - Yue Teng; Zhongfu Li; Tianxin Li; Yiran Li; Enqin Gong; Robert L.K. Tiong; Sha Liu (Energy and Buildings, 2024)

Investigation on Rock Fracturing in Presplit Blasting Under Various Initial Stresses - Kewei Liu; Xudong Li; Linqi Huang; Yanyan Sha; Jiacai Yang; Xinrui Zhao; Sizhou Ma; Zhixian Hong (Rock Mechanics and Rock Engineering, 2024)

A local rainfall-triggered giant landslide occurred in a region along a high-speed railway on the Qinghai–Tibetan Plateau - Qingpeng Li; Wenhui Liu; Renjie He; Chunye Ying; Hairui Liu; Zengning Dou; Yabing Liu; Sha Yang; Xianteng Song (Journal of Mountain Science, 2024)

Nine-year fertilization promoted C sink and mediated microbial nutrient utilization in alpine meadow soil aggregates - Leilei Qiao; Huakun Zhou; Zhanhui Wang; Wenjing Chen; Yuanze Li; Yang Wu; Guobin Liu; Sha Xue (Applied Soil Ecology, 2024)

Oxidase-like nanozymes-driven colorimetric, fluorescence and electrochemiluminescence assays for pesticide residues - Sha Liu; Chao Nie; Fengjiao He; Guojian Wu; Heng Wang; Si Li; Chenxing Du; Zhi Zheng; Jieshun Cheng; Yizhong Shen; Jie Cheng (Trends in Food Science & Technology, 2024)

Fabrication of high mechanical strength and high porosity PVDF isoporous membranes based on inverse opal photonic crystals - Sha Fan; Yu Wang; Xinyi Hong; Gaofeng Liu; Chengcai Li; Hailin Zhu; Bin Yu; Guojin Liu (Journal of Water Process Engineering, 2024)

Innovative insights into dry fermented sausages flavor: Unraveling the impact of varied lactobacillus genera-driven fermentation - Sha-sha Zheng; Ying-ying Hu; Li-jun Tan; Liu Yang; Chun-yu Wang; Bao-cai Xu (Food Bioscience, 2024)

Adenylate kinase phosphate energy shuttle underlies energetic communication in flagellar axonemes - Huan Wu; Yanman Zhang; Yuqian Li; Shuya Sun; Jintao Zhang; Qingsong Xie; Yue Dong; Shushu Zhou; Xuan Sha; Kuokuo Li; Jinyi Chen; Xin Zhang; et al. (Science China Life Sciences, 2024)

High dimensional proteomic mapping of bone marrow immune characteristics in immune thrombocytopenia - Feng-Qi Liu; Qing-Yuan Qu; Ying Lei; Qi Chen; Yu-Xiu Chen; Meng-Lin Li; Xue-Yan Sun; Ye-Jun Wu; Qiu-Sha Huang; Hai-Xia Fu; Yuan Kong; Yue-Ying Li; et al. (Science China Life Sciences, 2024)

Automatic Segmentation of Intracranial Hemorrhage in Computed Tomography Scans with Convolution Neural Networks - Weijin Xu; Zhuang Sha; Tao Tan; Wentao Liu; Yifu Chen; Zhanying Li; Xipeng Pan; Rongcai Jiang; Huihua Yang (Journal of Medical and Biological Engineering, 2024)

Diatoms as indicators of environmental change in coastal areas: a case study in Lianjiang coast of East China Sea - Tong Li; Jihui Zhang; Dongling Li; Chengxu Zhou; Chenxi Liu; Hao Xu; Bing Song; Longbin Sha (Acta Oceanologica Sinica, 2024)

Combining rigid and deformable groups to construct a robust birefringent crystal for compact polarization components - Zhipeng Du; Xianyu Song; Wei Liu; Ziyi Wang; Hongyuan Sha; Qianting Xu; Yang Zhou; Yanqiang Li; Junhua Luo; Sangen Zhao (Science Bulletin, 2024)

SAD2 functions in plant pathogen Pseudomonas syringae pv tomato DC3000 defense by regulating the nuclear accumulation of MYB30 in Arabidopsis thaliana - Tiantian Shi; Yuan Zheng; Rui Wang; Sha Li; Andi Xu; Luoying Chen; Yuanhang Liu; Rong Luo; Chenchen Huang; Yinglu Sun; Jinfeng Zhao; Xiaoying Guo; et al. (Plant Science, 2024)

External carbon source as a viable tool for controlling antibiotics and antibiotic resistance genes (ARGs) in effluent: Influence on antibiotic removal and ARGs dissemination - Yining Qu; Peng Li; Yuxue Liu; Sha Dai; Yu Xie; Yiliang He (Journal of Environmental Management, 2024)

ZnO nanorod coatings attenuate antibiotic resistance genes (ARGs) on their surface biofilms in estuarine environment - Xing-pan Guo; Rong-rong Sha; Yu-cen Wang; Jia Yan; Bo Peng; Zuo-shun Niu; Wen-liang Liu; Xin Li; Yi Yang (Journal of Environmental Chemical Engineering, 2024)

LTA and PGN from Bacillus siamensis can alleviate soybean meal-induced enteritis and microbiota dysbiosis in Lateolabrax maculatus - Zi-Yan Liu; Hong-Ling Yang; Guo-He Cai; Sha Li; Ji-Dan Ye; Chun-Xiao Zhang; Yun-Zhang Sun (Fish & Shellfish Immunology, 2024)

Temporal-spatial characteristics and sources of heavy metals in bulk deposition across China - Xin Ma; Zhipeng Sha; Yunzhe Li; Ruotong Si; Aohan Tang; Andreas Fangmeier; Xuejun Liu (Science of The Total Environment, 2024)

Self-assembly and aggregation behavior of temperature-controlled modified glycinin and d-galactose colloidal particles - Shiqi Tang; Panling Liu; Sha Zhu; Tianzhan Kou; Yang Li; Lianzhou Jiang; Baokun Qi (Food Chemistry, 2024)

Enhancement of foamability parallel with foam stability of rice dreg protein by ions-induced treatment based on pH shifting: Interfacial properties and interaction mechanism - Sha Yang; Jun Chen; Gaomeng Xu; Lizhen Deng; Changhong Li; Ti Li; Chengmei Liu; Taotao Dai (Food Hydrocolloids, 2024)

Visible-light-initiated air-oxygenation of 5-hydroxymethylfurfural to maleic acid by iron(III) chloride - Yabo Qi; Sha Luo; Wei Li; Shujun Li; Zhijun Chen; Bing Tian; Shouxin Liu (Chemical Engineering Journal, 2024)

Typical antibiotic resistance genes and their association with driving factors in the coastal areas of Yangtze River Estuary - Qiuhong Xu; Shuguang Liu; Sha Lou; Junbiao Tu; Xin Li; Yuchen Jin; Wenjun Yin; Larisa Dorzhievna Radnaeva; Elena Nikitina; Aleksei Nikolavich Makhinov; José Tavares Araruna; Irina Viktorovna Fedorova (Environmental Science and Pollution Research, 2024)

The association between per-/polyfluoroalkyl substances in serum and thyroid function parameters: A cross-sectional study on teenagers living near a Chinese fluorochemical industrial plant - Lin-Na Xie; Xiao-Chen Wang; Li-Qin Su; Sai-Sai Ji; Wen Gu; Holly Barrett; Xiao-Jie Dong; Hui-Juan Zhu; Sha-Sha Hou; Zhen-Huan Li; Yi-Lin Liu; Ling Zhang; et al. (Science of The Total Environment, 2024)

Arabidopsis HAPLESS13/AP-1µ is critical for pollen sac formation and tapetal function - Gui-Min Yin; Yi-Ru Fang; Jia-Gang Wang; Yue Liu; Xiaojiao Xiang; Sha Li; Yan Zhang (Plant Science, 2024)

Designed synthesis N-doped sulfonated bifunctional catalyst for efficient 5-hydroxymethylfurfural production: A pyridinic N-triggered proton-shift mechanism at basic sites - Yu Yin; Yabo Qi; Chunhui Ma; Zhenwei Wu; Wei Li; Sha Luo; Shouxin Liu (Fuel, 2024)

Transport of per-/polyfluoroalkyl substances from leachate to groundwater as affected by dissolved organic matter in landfills - Jia Li; Haoqun Sha; Weijiang Liu; Ying Yuan; Ganghui Zhu; Fanhua Meng; Beidou Xi; Wenbing Tan (Environmental Research, 2024)

Promotion of rice seedlings growth and enhancement of cadmium immobilization under cadmium stress with two types of organic fertilizer - Liang Chen; Jingjing Ma; Sha Xiang; Lihong Jiang; Ying Wang; Zhihuan Li; Xianjing Liu; Shuyang Duan; Yuan Luo; Yunhua Xiao (Environmental Pollution, 2024)

Effects of in-situ stress on rock cracking in presplit blasting - Xudong Li; Kewei Liu; Jiacai Yang; Tao Qiu; Yanyan Sha (Computers and Geotechnics, 2024)

Synchronous removal of oxytetracycline and Cr(Ⅵ) in Fenton-like photocatalysis process driven by MnFe2O4/g-C3N4: Performance and mechanisms - Yujuan Li; Sha Wang; He Guo; Jian Zhou; Yue Liu; Tiecheng Wang; Xianqiang Yin (Chemosphere, 2024)

Analysis of alternative splicing provides insights into its vital roles in immune responses of half-smooth tongue sole (Cynoglossus semilaevis) against Vibrio anguillarum - Sen Han; Suxu Tan; Hongning Liu; Ningning Wang; Xinbao Liu; Zhujun Li; Zhendong Wu; Jie Ma; Wenwen Wang; Kunpeng Shi; Zhenxia Sha (Aquaculture, 2024)

Ni-Pt nanozyme-mediated relaxation and colorimetric sensor for dual-modality detection of norovirus - Lei Huang; Xue Zhang; Zefeng Mao; Sha Liu; Yanchun Li; Shuyue Ren; Huanying Zhou; Baolin Liu; Zhixian Gao (Science of The Total Environment, 2024)

LA-ICPMS in situ U Pb dating of skarn garnet from the Tongling ore district of eastern China - Ting Liang; Shao-Bing Zhang; Xiao-Yong Yang; Zhen-Xin Li; Xing-Yu Yao; Yu Wang; Sha-Sha Liu (Lithos, 2024)

Pigmentiphaga kullae CHJ604 improved the growth of tobacco by degrading allelochemicals and xenobiotics in continuous cropping obstacles - Jia-Xi Xiong; Ling-Shan Du; Na-Na Li; Xiu-Ting Wu; Yang Xiang; Sha Li; Lei Zou; Dongqi Liu; Duo Huang; Ze Feng Xie; Ying Wang; Jinhua Li; et al. (Journal of Hazardous Materials, 2024)

Preparation and evaluation of liquorice (Glycyrrhiza uralensis) and ginger (Zingiber officinale) kombucha beverage based on antioxidant capacities, phenolic compounds and sensory qualities - Ruo-Gu Xiong; Dan-Dan Zhou; Jin Cheng; Si-Xia Wu; Adila Saimaiti; Si-Yu Huang; Qing Liu; Ao Shang; Hua-Bin Li; Sha Li (International Journal of Gastronomy and Food Science, 2024)

Mn-CaCO3-based nanosystem for augmented sonodynamic-chemodynamic immunotherapy via PI3K/Akt signaling pathway - Mashiti Sha; Huansong Li; Yangsui Liu; Cong Tang; Xue Bai; Yun Wang; Bo Yuan; Kairui Liu; Xiaoning Gao; Jun Yan; Silong Wei; Jin Chang; et al. (Chemical Engineering Journal, 2024)

High-solution emission characters and health risks of volatile organic compounds for sprayers in automobile repair industries - Zhanxia Du; Hanbing Li; Lei Nie; Zhen Yao; Xinmin Zhang; Yuting Liu; Sha Chen (Environmental Science and Pollution Research, 2024)

Neuroticism and openness exhibit an anti-correlation pattern to dissociable default mode network: using resting connectivity and structural equation modeling analysis - Shengwen Zhi; Wentao Zhao; Yifei Huang; Yue Li; Xiao Wang; Jing Li; Sha Liu; Yong Xu (Brain Imaging and Behavior, 2024)

Peroxymonosulfate activation by trace iron(III) porphyrin for facile degradation of organic pollutants via nonradical oxidation - Lu Liu; Jingping Hu; Jianjian Tang; Sijing Chen; Longsheng Wu; Zhen Li; Huijie Hou; Sha Liang; Jiakuan Yang (Chemosphere, 2024)

Enhanced O/W emulsion stability and betanin protection using yeast protein and chitooligosaccharide: Comparative insights from complex coacervation and layer-by-layer methods - Jiangnan Hu; Rui Yang; Runxuan Chen; Chang Liu; Xinmei Sha; Ku Li; Hui Guo; Yuyu Zhang (Food Hydrocolloids, 2024)

Paraprobiotic and postbiotic forms of Bacillus siamensis improved growth, immunity, liver and intestinal health in Lateolabrax maculatus fed soybean meal diet - Zi-Yan Liu; Hong-Ling Yang; Sha Li; Guo-He Cai; Ji-Dan Ye; Chun-Xiao Zhang; Yun-Zhang Sun (Fish & Shellfish Immunology, 2024)

Phenethyl isothiocyanate induces cytotoxicity and apoptosis of porcine kidney cells through Mitochondrial ROS-associated ERS pathway - Yuanyuan Zhu; Qiurong Xu; Ruili Zou; Sha Liu; Ran Tao; Shuiping Liu; Xiaowen Li; Lixin Wen; Jing Wu; Ji Wang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Histone methyltransferase KMT2D inhibits ENKTL carcinogenesis by epigenetically activating SGK1 and SOCS1 - Yue-Hua Zhang; Qing Tao; Wen-Yan Zhang; Sha Zhao; Wei-Ping Liu; Li-Min Gao (Genes & Genomics, 2024)

A spatial projection pursuit model for identifying comprehensive urban vitality on blocks using multisource geospatial data - Zhiran Zhang; Jiping Liu; Chengyu Wang; Yangyang Zhao; Xizhi Zhao; Pengpeng Li; Dexuan Sha (Sustainable Cities and Society, 2024)

Mitigation of reactive nitrogen loss from arable soils through microbial inoculant application: A meta-analysis - Jiyang Lv; Xiayan Zhang; Zhipeng Sha; Shouguo Li; Xian Chen; Yongliang Chen; Xuejun Liu (Soil and Tillage Research, 2024)

Effects of miR-722 on gene expression and alternative splicing in the liver of half-smooth tongue sole after infection with Vibrio anguillarum - Hongning Liu; Suxu Tan; Sen Han; Xinbao Liu; Zhujun Li; Ningning Wang; Zhendong Wu; Jie Ma; Kunpeng Shi; Wenwen Wang; Zhenxia Sha (Fish & Shellfish Immunology, 2024)

High Lewis acidity catalyst for direct depolymerization of microcrystalline cellulose to 5- hydroxymethylfurfural: Reaction optimization by central composite design - Yu Yin; Chunhui Ma; Wei Li; Sha Luo; Zhanshuo Zhang; Shouxin Liu (Biomass and Bioenergy, 2024)

Comparative transcriptomic and lipidomic analysis of oleic environment adaptation in Saccharomyces cerevisiae: insight into metabolic reprogramming and lipid membrane expansion - Yi Shen; Xia Ke; Zi-Hao Pan; Li-Sha Cao; Zhi-Qiang Liu; Yu-Guo Zheng (Systems Microbiology and Biomanufacturing, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

JAZ1 gene regulates starch biosynthesis and changes physicochemical properties in wheat grains - Sha-Sha Yuan; Peng Fan; Dan-Dan Zhang; Hai-Tao Liu; Peng-Fei Wang; Tian-Cai Guo; Ge-Zi Li; Yong-Hua Wang; Guo-Zhang Kang (Food Bioscience, 2023)

Dietary supplementation with American ginseng dietary fiber ameliorates intestinal mucosal barrier injury in immunosuppressed mice - Jiyue Sha; Zhengbo Liu; Hongxia Yu; Xiaohui Huo; Jiajia Wang; Yuanyuan Duan; Wei Li; Di Qu; Zhiman Li; Jianbo Chen; Xueqing Li; Yinshi Sun (Food Bioscience, 2023)

Recent progress on atomic-scale modulation of single-atom-based catalysts for electrocatalytic CO2 reduction - Yingjie Liu; Sha Bai; Qian Li; Zhaohui Wu; Tianyang Shen; Jinfeng Chu; Yu-Fei Song (Chemical Engineering Journal, 2023)

Effects of Long-Term Warming on Microbial Nutrients Limitation of Soil Aggregates on the Qinghai-Tibet Plateau - Wenjing Chen; Huakun Zhou; Leilei Qiao; Yuanze Li; Yang Wu; Jiaying Zhai; Guobin Liu; Sha Xue (Journal of Soil Science and Plant Nutrition, 2023)

Histological Assessment and Transcriptome Analysis Provide Insights into the Toxic Effects of Perfluorooctanoic Acid to Juvenile Half Smooth Tongue Sole Cynoglossus semilaevis - Min Zhan; Kunpeng Shi; Xue Zhang; Qingxin Fan; Qian Xu; Xinbao Liu; Zhujun Li; Hongning Liu; Yanting Xia; Zhenxia Sha (Journal of Ocean University of China, 2023)

Dietary nano-selenium improves health of liver and intestine of grass carp Ctenopharyngodon idella after overwintering - Limin Ye; Sha Liu; Xiaotian Zhang; Chi Wang; Pengju Li; Cheng Zhang; Hong Ji; Haibo Yu (Animal Feed Science and Technology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Occurrence of sulfonamides and tetracyclines in the coastal areas of the Yangtze River (China) Estuary - Shuguang Liu; Xin Li; Sha Lou; Qiuhong Xu; Yuchen Jin; Radnaeva Larisa Dorzhievna; Nikitina Elena; Makhinov Aleksei Nikolavich; Araruna José Tavares; Fedorova Irina Viktorovna (Environmental Science and Pollution Research, 2023)

Boerechalasins A–G, cytochalasans from the fungus Boeremia exigua with anti-inflammatory and cytotoxic activities - Si-Qiong Teng; Xiao-Fang Zhang; Hong-Fei Li; Xin-Wen Luo; Yang-Sha Zhou; Hui Liu; Ji-Kai Liu; Tao Feng (Phytochemistry, 2023)

Effects of deterministic assembly of communities caused by global warming on coexistence patterns and ecosystem functions - Wenjing Chen; Huakun Zhou; Yang Wu; Jie Wang; Ziwen Zhao; Yuanze Li; Leilei Qiao; Kelu Chen; Guobin Liu; Coen Ritsema; Violette Geissen; Xue Sha (Journal of Environmental Management, 2023)

Direct identification of total and missing OH reactivities from light-duty gasoline vehicle exhaust in China based on LP-LIF measurement - Xuehui Liu; Zibing Yuan; Qing'e Sha; Shengrong Lou; Hongli Wang; Xin Li; Junyu Zheng; Bin Yuan; Min Shao (Journal of Environmental Sciences, 2023)

Adding nitrification inhibitors to N fertilisers induces rhizosphere acidification and enhances P acquisition: A meta-analysis - Shouguo Li; Yanwei Liu; Zhipeng Sha; Shikang Li; Qiliang Yang (European Journal of Agronomy, 2023)

Interrogating greenhouse gas emissions of different dietary structures by using a new food equivalent incorporated in life cycle assessment method - Mengrong Zhang; Hanbing Li; Sha Chen; Yingying Liu; Sumei Li (Environmental Impact Assessment Review, 2023)

Understanding how microbial electrolysis cell assisted anaerobic digestion enhances triclocarban dechlorination in sludge - Sha Long; Qizi Fu; Zhixiang Hao; Luyang Sun; Zihan Li; Yike Guo; Xuran Liu; Fengming Song; Dongbo Wang; Wenming Wang (Chemical Engineering Journal, 2023)

Carrier-free 5-Fu nanoparticle-mediated domestication therapy for scar treatment: A preclinical and first-in-human study - Peng He; Sha Yi; Jianzhong Zhang; Chengchao Chu; Xuqi Peng; Changhong Li; Xinfei Sun; Yang Zhang; Hongwei Cheng; Xia Xiong; Gang Liu (Chemical Engineering Journal, 2023)

A tumor microenvironment responsive titanium-based nanosonosensitizer for combination sonodynamic-immunotherapy with calcium ion overload - Cong Tang; Huansong Li; Mashiti Sha; Jianyin Song; Xue Bai; Kairui Liu; Yangsui Liu; Bo Yuan; Jun Yan; Jin Chang; Jun Kang (Chemical Engineering Journal, 2023)

Characterization of three new plant growth-promoting microbes and effects of the interkingdom interactions on plant growth and disease prevention - Yuan Tian; Yang Liu; Constantine Uwaremwe; Xia Zhao; Liang Yue; Qin Zhou; Yun Wang; Lam-Son Phan Tran; Weiqiang Li; Gaofeng Chen; Yuexia Sha; Ruoyu Wang (Plant Cell Reports, 2023)

Inflammatory reaction and immune response of half-smooth tongue sole (Cynoglossus semilaevis) after infection with Vibrio anguillarum - Wenwen Wang; Qian Xu; Shaoqing Zang; Xinbao Liu; Hongning Liu; Zhujun Li; Qingxin Fan; Suxu Tan; Kunpeng Shi; Yanting Xia; Zhenxia Sha (Fish & Shellfish Immunology, 2023)

Probiotic components of Bacillus siamensis LF4 mitigated β-conglycinin caused cell injury via modulating TLR2/MAPKs/NF-κB signaling in Lateolabrax maculatus - Zi-Yan Liu; Hong-Ling Yang; Sha Li; Guo-He Cai; Ji-Dan Ye; Chun-Xiao Zhang; Yun-Zhang Sun (Fish & Shellfish Immunology, 2023)

Ni-CeO2 nanocomposite with enhanced metal-support interaction for effective ammonia decomposition to hydrogen - Hongwang Liu; Yining Zhang; Sibao Liu; Sha Li; Guozhu Liu (Chemical Engineering Journal, 2023)

α2,3-Sialylation with Fucosylation Associated with More Severe Anti-MDA5 Positive Dermatomyositis Induced by Rapidly Progressive Interstitial Lung Disease - Rongrong Zhang; Li Guo; Jichen Sha; Shuwai Chang; Jiangfeng Zhao; Kaiwen Wang; Jiucun Wang; Jianxin Gu; Jing Liu; Shifang Ren (Phenomics, 2023)

Primary cutaneous cryptococcosis presenting as ulcers in solid organ transplant recipient - Ying Tang; Wenying Cai; Li Lin; Jiahao Li; Hsingmei Liu; Liyan Xi; Sha Lu (Mycopathologia, 2023)

Epidemiology and Clinical Findings of Tinea Capitis: A 23-Year Retrospective, Single-Center Study in Guangzhou, China - Wenying Cai; Junhao Huang; Jiahao Li; Li Lin; Liyan Xi; Junmin Zhang; Xiqing Li; Zhen Zhou; Ying Tang; Hsingmei Liu; Jing Zhang; Sha Lu (Mycopathologia, 2023)

Pediatric tinea capitis in Jilin Province: analyzing previous results from a new perspective - Jing Zeng; Shuang Wang; Lu Guo; Sha Lv; Baihui Shan; Zhe Liu; Fuqiu Li (Mycopathologia, 2023)

Long-term warming impacts grassland ecosystem function: Role of diversity loss in conditionally rare bacterial taxa - Wenjing Chen; Huakun Zhou; Yang Wu; Jie Wang; Ziwen Zhao; Yuanze Li; Leilei Qiao; Kelu Chen; Guobin Liu; Coen Ritsema; Violette Geissen; Xinrong Guo; et al. (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Effect of plant-soil feedback on soil microbial co-occurrence network depends on the stage of secondary succession - Zemin Ai; Yi Deng; Xinghua Li; Jiaoyang Zhang; Hongfei Liu; Hongwei Xu; Guobin Liu; Xue Sha (Rhizosphere, 2023)

Improving air quality through urban form optimization: A review study - Sha Li; Bin Zou; Xuying Ma; Ning Liu; Zixin Zhang; Manman Xie; Lu Zhi (Building and Environment, 2023)

The biocontrol agent Bacillus velezensis T-5 changes the soil bacterial community composition by affecting the tomato root exudate profile - Yian Gu; Weina Liang; Zhidan Li; Sijie Liu; Sun Liang; Peng Lei; Rui Wang; Nan Gao; Sha Li; Zongqi Xu; Hong Xu (Plant and Soil, 2023)

Two new bibenzyls from Pleione grandiflora (Rolfe) Rolfe and their antioxidant activity - Wei Li; Jia-Rui Fu; Li-Jun Zheng; Lin Ni; Jun-Qing Liu; Jun-Wen Zhai; Zhuang Zhou; Sha-Sha Wu (Natural Product Research, 2023)

Acer truncatum leaves reduce lipid accumulation and improve liver and intestine health of grass carp (Ctenopharyngodon idella) fed with high-fat diet - Limin Ye; Xiaotian Zhang; Chi Wang; Sha Liu; Pengju Li; Cheng Zhang; Qinfeng Gao; Hong Ji; Haibo Yu (Aquaculture, 2023)

CRISPR/Cas9-mediated BoaAOP2s editing alters aliphatic glucosinolate side-chain metabolic flux and increases the glucoraphanin content in Chinese kale - Hao Zheng; Wenli Huang; Xiangxiang Li; Huanhuan Huang; Qiao Yuan; Ruobin Liu; Hongmei Di; Sha Liang; Mengyu Wang; Mengyao Li; Zhi Huang; Yi Tang; et al. (Food Research International, 2023)

C5a drives the inflammatory response with bacterial dose effect by binding to C5aR1 in zebrafish infected with Aeromonas hydrophila - Xinbao Liu; Wenwen Wang; Suxu Tan; Hongning Liu; Zhujun Li; Ningning Wang; Jie Ma; Sen Han; Zhendong Wu; Kunpeng Shi; Zhenxia Sha (Fish & Shellfish Immunology, 2023)

Aptamer-controlled reversible colorimetric assay: High-activity bimetallic organic frameworks for the efficient sensing of marine biotoxins - Sha Liu; Yapeng Huo; Guanghua Li; Lei Huang; Tao Wang; Zhixian Gao (Chemical Engineering Journal, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Origin and diversification of a Himalayan orchid genus Pleione - Sha-Sha Wu; Ming-Tao Jiang; Jiang-lin Miao; Ming-He Li; Jie-Yu Wang; Li-Ming Shen; Dong-Hui Peng; Si-Ren Lan; Jun-Wen Zhai; Zhong-Jian Liu (Molecular Phylogenetics and Evolution, 2023)

The responses of ecosystem water use efficiency to CO2, nitrogen deposition, and climatic drivers across China - Xitian Cai; Luyi Li; Joshua B. Fisher; Zhenzhong Zeng; Sha Zhou; Xuezhi Tan; Bingjun Liu; Xiaohong Chen (Journal of Hydrology, 2023)

Corrigendum to “Generation of high-valent iron-oxo porphyrin cation radicals on hemin loaded carbon nanotubes for efficient degradation of sulfathiazole” [J. Hazard. Mater. 444 (2023) 130402] - Sijing Chen; Zhen Li; Longsheng Wu; Lu Liu; Jingping Hu; Huijie Hou; Sha Liang; Jiakuan Yang (Journal of Hazardous Materials, 2023)

Cation-deficient T-Nb2O5/graphene Hybrids synthesized via chemical oxidative etching of MXene for advanced lithium-ion capacitors - Lei Wang; Xiong Zhang; Chen Li; Yanan Xu; Yabin An; Wenjie Liu; Tao Hu; Sha Yi; Kai Wang; Xianzhong Sun; Yue Gong; Zhong-Shuai Wu; et al. (Chemical Engineering Journal, 2023)

Assessing decarbonization pathways of China’s heavy-duty trucks in a well-to-wheels perspective - Xingyu Xue; Jianxin Li; Xin Sun; Amir F. N. Abdul-Manan; Sha Du; Huanran Liu; Shujie Xu; Mingnan Zhao (The International Journal of Life Cycle Assessment, 2023)

Revealing an unrecognized role of free ammonia in sulfur transformation during sludge anaerobic treatment - Qizi Fu; Sha Long; Yunhao Xu; Yan Wang; Bentao Yang; Dandan He; Xuemei Li; Xuran Liu; Qi Lu; Dongbo Wang (Journal of Hazardous Materials, 2023)

Commensal Bacillus siamensis LF4 ameliorates β-conglycinin induced inflammation in intestinal epithelial cells of Lateolabrax maculatus - Zi-Yan Liu; Hong-Ling Yang; Xi-Yue Ding; Sha Li; Guo-He Cai; Ji-Dan Ye; Chun-Xiao Zhang; Yun-Zhang Sun (Fish & Shellfish Immunology, 2023)

Functionalized graphitic carbon nitride based catalysts in solar-to-chemical conversion for hydrogen peroxide production - Chao Liang; Xue-Min Wang; Wei Liu; Hui-Yun Liu; Da-Wei Huang; Yuan-Zheng Zhang; Kai-Hang Zhang; Li-Sha Jiang; Yu-Yu Jia; Cheng-Gang Niu (Chemical Engineering Journal, 2023)

Genome-wide Transcriptome Analysis Reveals the Gene Regulatory Network in Star Fruit Flower Blooming - Si Qin; Xiao-Ping Li; Chun-Mei Wu; Le You; Donghui Peng; Sagheer Ahmad; Hui Ren; Zhong-Jian Liu; Jun-Wen Zhai; Sha-Sha Wu (Tropical Plant Biology, 2023)

The mechanisms underpinning anthocyanin accumulation in a red-skinned bud sport in pear (Pyrus ussuriensis) - Weiting Liu; Yun Wei; Shoufeng Sha; Yaxiu Xu; Hongjian Li; Hui Yuan; Aide Wang (Plant Cell Reports, 2023)

2,4-Dinitrotoluene (2,4-DNT) exposure induces liver developmental damage and perturbs lipid metabolism and oxygen transport gene expression in zebrafish (Danio rerio) - Liangxia Su; Hang Sha; Jun Liu; Le Yu; Huanhuan Li; Rui Wang (Environmental Science and Pollution Research, 2023)

Numerical investigation on rock fragmentation under decoupled charge blasting - Xudong Li; Kewei Liu; Yanyan Sha; Jiacai Yang; Ruitao Song (Computers and Geotechnics, 2023)

Rational design of molecular phototheranostic platform for NIR-II fluorescence imaging guided chemodynamic-photothermal combined therapy - Gui-long Wu; Bin Sun; Yuxuan He; Xiaofeng Tan; Qi Pan; Sha Yang; Na Li; Minghui Wang; Peixian Wu; Fen Liu; Hao Xiao; Li Tang; et al. (Chemical Engineering Journal, 2023)

Response mechanisms of anaerobic fermentative sludge to zinc oxide nanoparticles during medium-chain carboxylates production from waste activated sludge - Chao Liu; Muhammad Usman; Mengyuan Ji; Jun Sha; Li Zhou; Bing Yan (Chemosphere, 2023)

Variations in soil aggregate stability and organic carbon stability of alpine meadow and shrubland under long-term warming - Leilei Qiao; Huakun Zhou; Zhanhui Wang; Yuanze Li; Wenjing Chen; Yang Wu; Guobin Liu; Sha Xue (CATENA, 2023)

lncRNA UCA1 inhibits mitochondrial dysfunction of skeletal muscle in type 2 diabetes mellitus by sequestering miR-143-3p to release FGF21 - Sha Huang; Kai Wu; Bingfa Li; Yuan Liu (Cell and Tissue Research, 2023)

MUSER and IPS telescopes for solar and space weather observations - Yihua Yan; Wei Wang; Linjie Chen; Fei Liu; Jin Fan; Zhijun Chen; Lihong Geng; Chengming Tan; Suli Ma; Sha Li; Cang Su; Jing Du; et al. (Advances in Space Research, 2023)

Nonmonotonic effect of CuO nanoparticles on medium-chain carboxylates production from waste activated sludge - Chao Liu; Haiqing Wang; Muhammad Usman; Mengyuan Ji; Jun Sha; Zhenda Liang; Lishan Zhu; Li Zhou; Bing Yan (Water Research, 2023)

Maternal exposure to 4-vinylcyclohexene diepoxide during pregnancy induces subfertility and birth defects of offspring in mice - Wei Song; Ang Li; Qian-Qian Sha; Shao-Yuan Liu; Yong Zhou; Chang-Yin Zhou; Xue Zhang; Xiao-Zhen Li; Jia-Xin Jiang; Fei Li; Chao Li; Heide Schatten; et al. (Science of The Total Environment, 2023)

Global assessment of nature’s contributions to people - Yanxu Liu; Bojie Fu; Shuai Wang; Jonathan R. Rhodes; Yan Li; Wenwu Zhao; Changjia Li; Sha Zhou; Chenxu Wang (Science Bulletin, 2023)

Genomic analysis of Marinimicrobium sp. C6131 reveals its genetic potential involved in chitin metabolism - Yan-Ru Dang; Xiao-Yu Zhang; Sha-Sha Liu; Ping-Yi Li; Xue-Bing Ren; Qi-Long Qin (Marine Genomics, 2023)

Generation of high-valent iron-oxo porphyrin cation radicals on hemin loaded carbon nanotubes for efficient degradation of sulfathiazole - Sijing Chen; Zhen Li; Longsheng Wu; Lu Liu; Jingping Hu; Huijie Hou; Sha Liang; Jiakuan Yang (Journal of Hazardous Materials, 2023)

Tumor microenvironment activated nanoreactors for chemiluminescence imaging-guided simultaneous elimination of breast tumors and tumor-resident intracellular pathogens - Xinxin Li; Ting Wu; Zefan Zhang; Sha Liu; Hongmei Cui; Zhongxiong Fan; Baodui Wang; Jun Hai (Chemical Engineering Journal, 2023)

Contribution of Tibetan Plateau ecosystems to local and remote precipitation through moisture recycling - Yan Li; Ru Xu; Kun Yang; Yanxu Liu; Shuai Wang; Sha Zhou; Zhao Yang; Xiaoming Feng; Chunyang He; Zhengjie Xu; Wenwu Zhao (Global Change Biology, 2023)
The ecosystems of the Tibetan Plateau (TP) provide multiple important ecosystem services that benefit both local populations and those beyond, such as through climate regulation services on precipitation for East Asia and China. However, the precipitation regulation service of the TP ecosystems for supplying moisture and maintaining precipitation is yet to be evaluated. In this study, we used the moisture recycling framework and a moisture tracking model to quantify the precipitation regulation services of TP ecosystems for their contribution to precipitation. We found TP ecosystems contributed substantially to local and downwind precipitation, with a contribution of 221 mm/year for the TP and neighboring areas through evapotranspiration (ET) (104 mm/year through transpiration), declined to

Iron-calcium reinforced solidification of arsenic alkali residue in geopolymer composite: Wide pH stabilization and its mechanism - Yingfei Sun; Pan Zhang; Zhen Li; Jing Chen; Yan Ke; Jingping Hu; Bingchuan Liu; Jiakuan Yang; Sha Liang; Xintai Su; Huijie Hou (Chemosphere, 2023)

Study on sex-linked region and sex determination candidate gene using a high-quality genome assembly in yellow drum - Sha Sun; Chaowei Song; Fang Han; Qiwei He; Jieping Liu; Sen Zhang; Wei Han; Kun Ye; Zhaofang Han; Zhiyong Wang; Wanbo Li (Aquaculture, 2023)

A critical review on microbial ecology in the novel biological nitrogen removal process: Dynamic balance of complex functional microbes for nitrogen removal - Hong Chen; Ke Liu; Enzhe Yang; Jing Chen; Yanling Gu; Sha Wu; Min Yang; Hong Wang; Dongbo Wang; Hailong Li (Science of The Total Environment, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

FeCl3 and Fe2(SO4)3 differentially reduce Cd uptake and accumulation in Polish wheat (Triticum polonicum L.) seedlings by exporting Cd from roots and limiting Cd binding in the root cell walls - Qin Yao; Weiping Li; Ying Liu; Yiran Cheng; Xue Xiao; Dan Long; Jian Zeng; Dandan Wu; Lina Sha; Xing Fan; Houyang Kang; Haiqin Zhang; et al. (Environmental Pollution, 2023)

Effect of plant–plant interactions and drought stress on the response of soil nutrient contents, enzyme activities and microbial metabolic limitations - Lie Xiao; Xuxu Min; Guobin Liu; Peng Li; Sha Xue (Applied Soil Ecology, 2023)

Substitution of soybean meal with Clostridium autoethanogenum protein in grass carp (Ctenopharygodon idella) diets: Effects on growth performance, feed utilization, muscle nutritional value and sensory characteristics - Rongrong Xue; Handong Li; Sha Liu; Zechao Hu; Qin Wu; Hong Ji (Animal Feed Science and Technology, 2023)

Soil biochemical index-based assessment of the effect of drought stress on the rhizosphere soil quality in three typical grass species in the Loess Plateau, China - Lie Xiao; Meng Zhao; Guobin Liu; Peng Li; Fangyuan Liu; Sha Xue (Journal of Soils and Sediments, 2022)

Long-term warming does not affect soil ecoenzyme activity and original microbial nutrient limitation on the Qinghai—Tibet Plateau - Yuanze Li; Huakun Zhou; Wenjing Chen; Yang Wu; LeiLei Qiao; ZiRan Yan; GuoBin Liu; Sha Xue (Soil Ecology Letters, 2022)

Dynamic evaluation of environmental impact for three-way catalytic converter with temporal variation life cycle method - Yingying Liu; Hanbing Li; Sha Chen; Yana Zhang; He Lv; Shuqi Yan; Yipei Li; Zunwen Liu (The International Journal of Life Cycle Assessment, 2022)

Abrupt fluctuations in North Pacific Intermediate Water modulated changes in deglacial atmospheric CO2 - Yanguang Liu; Yue Qiu; Dongling Li; Antonina V. Artemova; Yuying Zhang; Aleksandr A. Bosin; Sergey A. Gorbarenko; Qingsong Liu; Debo Zhao; Longbin Sha; Yi Zhong (Frontiers in Marine Science, 2022)
As a major reservoir of heat and CO 2 , the Pacific Ocean is an important component of the global climate system, but the nature of its circulation under different climatic conditions remains poorly understood. We present sedimentary records of surface water hydrography and nutrient dynamics from the subarctic Pacific Ocean, with the aim of investigating changes in sea-ice coverage, biological productivity, and sea surface temperature in the subarctic Northwest Pacific since 32 kyr. Our records indicate an enhanced North Pacific surface water stratification from the last glacial to Heinrich Stadial 1, which generally limited the siliceous productivity supply to the surface water. A productivity peak during the Bølling/Allerød warm interval was associated with an increase in the atmospheric p CO 2 , and it was driven by the increased supply of nutrient- and CO 2 -rich waters. This process can be attributed to the collapse of the North Pacific Intermediate Water formation at the onset of the Bølling/Allerød interstadial. Moreover, a northward shift of the westerly winds and the gyre boundary could have modulated the expansion of the subpolar gyre, driving changes in poleward heat transport, biogeochemistry, and the hydroclimate of the North Pacific. Our results are consistent with modern evidence for a northward shift of the westerlies in response to global warming, which will likely result in CO 2 outgassing from the subarctic Pacific Ocean in the future.

Disassociated and concurrent structural and functional abnormalities in the drug-naïve first-episode early onset schizophrenia - Qiang Li; Sha Liu; Xiaohua Cao; Zexuan Li; Yun-shuang Fan; Yanfang Wang; Jiaojian Wang; Yong Xu (Brain Imaging and Behavior, 2022)
Schizophrenia which is an abnormally developmental disease has been widely reported to show abnormal brain structure and function. Enhanced functional integration is a predominant neural marker for brain mature. Abnormal development of structure and functional integration may be a biomarker for early diagnosis of schizophrenia. Fifty-five patients with early onset schizophrenia (EOS) and 79 healthy controls were enrolled in this study. Voxel-based morphometry (VBM) and functional connectivity density (FCD) were performed to explore gray matter volume (GMV) lesion, abnormal functional integration, and concurrent structural and functional abnormalities in the brain. Furthermore, the relationships between abnormalities structural and function and clinical characteristics were evaluated in EOS. Compared with healthy controls, EOS showed significantly decreased GMV in the bilateral OFC, frontal, temporal, occipital, parietal and limbic system. EOS also showed decreased FCD in precuneus and increased FCD in cerebellum. Moreover, we found concurrent changes of structure and function in left lateral orbitofrontal cortex (lOFC). Finally, correlation analyses did not find significant correlation between abnormal neural measurements and clinical characteristic in EOS. The results reveal disassociated and bound structural and functional abnormalities patterns in EOS suggesting structural and functional measurements play different roles in delineating the abnormal patterns of EOS. The concurrent structural and functional changes in lOFC may be a biomarker for early diagnosis of schizophrenia. Our findings will deepen our understanding of the pathophysiological mechanisms in EOS.

A Shuttling Protein Kank1 Plays Important Role in the Sex Determination in Yellow Drum - Sha Sun; Jieping Liu; Sen Zhang; Qiwei He; Wei Han; Kun Ye; Fang Han; Wanbo Li; Zhiyong Wang (Frontiers in Marine Science, 2022)
Sex is one of the most important scientific topics, and the existence of sex dimorphism is a conserved feature in vertebrate taxa. The research on sex-determining genes and sex chromosome evolution is a hot topic in biology. The majority of sex-determining genes expressed in somatic cells, and reciprocal interactions between germ cells and somatic cells, are important for gonadal differentiation. However, the knowledge of how signals are transmitted between somatic cells and germ cells remains unclear. In this study, we confirmed the 36 dph was a sex determination critical stage in yellow drum through transcriptome analysis at the early development stages. We further found that Kank1 participated in the germ cells’ motility process in yellow drum through KEGG pathway analysis together with protein-protein interaction network. With the dual-luciferase reporter assay, we detected that Kank1 increased the transcription of dmrt1_Luc gene in CHO cells and 293T cells. Additionally, we observed that Kank1 was not only expressed in the cytoplasm but also in the nucleus in CHO cells through a fluorescence microscope. These results suggest that Kank1 acts as a shuttling protein as in humans and may play a difunctional role at the early gonad development stage in yellow drum, and it not only participated in the germ cells’ motility but also increased the expression of dmrt1 in yellow drum.

Activating PIK3CA postzygotic mutations in segmental overgrowth of muscles with bone involvement in the body extremities - Wen Tian; Liying Sun; Qi Zhang; Junhui Zhao; Yang Guo; Wenyao Zhong; Liu Liu; Katia Meirelles; Sha Tang; Jing Zhang; Yingzhao Huang; Yuehan Yin; et al. (Molecular Genetics and Genomics, 2022)

Similarity and Dissimilarity Regularized Nonnegative Matrix Factorization for Single-Cell RNA-seq Analysis - Ya-Li Zhu; Sha-Sha Yuan; Jin-Xing Liu (Interdisciplinary Sciences: Computational Life Sciences, 2022)

What are more important for aftershock spatial distribution prediction, features, or models? A case study in China - Sha Zhao; Haiyan Wang; Yan Xue; Yilin Wang; Shijian Li; Jie Liu; Gang Pan (Journal of Seismology, 2022)

Biogeography of culturable marine bacteria from both poles reveals that ‘everything is not everywhere’ at the genomic level - Qi‐Long Qin; Zhi‐Bin Wang; Qian‐Qian Cha; Sha‐Sha Liu; Xue‐Bing Ren; Hui‐Hui Fu; Mei‐Ling Sun; Dian‐Li Zhao; Andrew McMinn; Yin Chen; Xiu‐Lan Chen; Yu‐Zhong Zhang; et al. (Environmental Microbiology, 2022)
Summary Based on 16S rRNA gene analyses, the same bacterial operational taxonomic units (OTUs) are common to both the Arctic and Antarctic oceans, supporting the concept ‘everything is everywhere’. However, whether the same OTUs from both poles have identical genomes, i.e. whether ‘everything is still everywhere’ at the genomic level has not yet been examined systematically. Here, we isolated, sequenced and compared the genomes of 45 culturable marine bacteria belonging to three genera of Salinibacterium , Psychrobacter and Pseudoalteromonas from both polar oceans. The bacterial strains with identical 16S rRNA genes were common to both poles in every genus, and four identical genomes were detected in the genus Salinibacterium from the Arctic region. However, no identical genomes were observed from opposite poles in this study. Our data, therefore, suggest that ‘everything is not everywhere’ at the genomic level. The divergence time between bacteria is hypothesized to exert a strong impact on the bacterial biogeography at the genomic level. The geographical isolation between poles was observed for recently diverged, highly similar genomes, but not for moderately similar genomes. This study thus improves our understanding of the factors affecting the genomic‐level biogeography of marine microorganisms isolated from distant locations.

Biomarker responses and histological damage in the gill, liver, and gonad of Cyprinus carpio with benzo(a)pyrene exposure - Weilai Sha; Fengsen Cai; Yu Li; Ying Wang; Chunchen Liu; Renjun Wang; Peike Gao (Environmental Science and Pollution Research, 2021)

Carbonic Anhydrase III Attenuates Hypoxia-Induced Apoptosis and Activates PI3K/Akt/mTOR Pathway in H9c2 Cardiomyocyte Cell Line - Hua Li; Yibin Liu; Sha Tang; Jie Hu; Qiuling Wu; Yang Wei; Ming Niu (Cardiovascular Toxicology, 2021)

Genetic control and phenotypic characterization of panicle architecture and grain yield-related traits in foxtail millet (Setaria italica) - Hui Zhi; Qiang He; Sha Tang; Junjun Yang; Wei Zhang; Huifang Liu; Yanchao Jia; Guanqing Jia; Aiying Zhang; Yuhui Li; Erhu Guo; Ming Gao; et al. (Theoretical and Applied Genetics, 2021)

Traits, strategies, and niches of liana species in a tropical seasonal rainforest - Qi Liu; Frank J. Sterck; Jiao-Lin Zhang; Arne Scheire; Evelien Konings; Min Cao; Li-Qing Sha; Lourens Poorter (Oecologia, 2021)
Plant functional traits and strategies hold the promise to explain species distribution, but few studies have linked multiple traits to multiple niche dimensions (i.e., light, water, and nutrients). Here, we analyzed for 29 liana species in a Chinese tropical seasonal rainforest how: (1) trait associations and trade-offs lead to different plant strategies; and (2) how these traits shape species’ niche dimensions. Eighteen functional traits related to light, water, and nutrient use were measured and species niche dimensions were quantified using species distribution in a 20-ha plot combined with data on canopy gaps, topographic water availability, and soil nutrients. We found a tissue toughness spectrum ranging from soft to hard tissues along which species also varied from acquisitive to conservative water use, and a resource acquisition spectrum ranging from low to high light capture and nutrient use. Intriguingly, each spectrum partly reflected the conservative–acquisitive paradigm, but at the same time, the tissue toughness and the resource acquisition spectrum were uncoupled. Resource niche dimensions were better predicted by individual traits than by multivariate plant strategies. This suggests that trait components that underlie multivariate strategy axes, rather than the plant strategies themselves determine species distributions. Different traits were important for different niche dimensions. In conclusion, plant functional traits and strategies can indeed explain species distributions, but not in a simple and straight forward way. Although the identification of global plant strategies has significantly advanced the field, this research shows that global, multivariate generalizations are difficult to translate to local conditions, as different components of these strategies are important under different local conditions.

Cellulomonas taurus sp. nov., a novel bacteria with multiple hydrolase activity isolated from livestock, and potential application in wastewater treatment - Sha-Sha Zhang; Jian-Feng Xu; Xiao-LI Sun; Wei Guo; Zeng-Shan Liu (Antonie van Leeuwenhoek, 2021)

QTL mapping for foxtail millet plant height in multi-environment using an ultra-high density bin map - Qiang He; Hui Zhi; Sha Tang; Lu Xing; Suying Wang; Haigang Wang; Aiying Zhang; Yuhui Li; Ming Gao; Haijin Zhang; Guoqiu Chen; Shutao Dai; et al. (Theoretical and Applied Genetics, 2021)

The effect of aging on VEGF/VEGFR2 signal pathway genes expression in rat liver sinusoidal endothelial cell - Wan-Li Wang; Xing-Long Zheng; Qing-Shan Li; Wen-Yan Liu; Liang-Shuo Hu; Huan-Chen Sha; Kun Guo; Yi Lv; Bo Wang (Molecular and Cellular Biochemistry, 2021)

Treatment of CML-transformed B Cell Acute Lymphoblastic Leukemia (B-ALL) in Adults with Anti-CD19 Chimeric Antigen Receptor T Cell (CAR T) Therapy - Fang Liu; Sha Sha; Gina Ma; Yi Su; Yisong Xiong; Guangcui He; Yecheng Li; William M. Hanes; William Tse (Stem Cell Reviews and Reports, 2020)

Association of in-hospital intensive statins dosage and death in arteriosclerotic cardiovascular disease with percutaneous coronary intervention: insights of multicentre cohort from China - Peng-yuan Chen; Yuan-hui Liu; Chong-yang Duan; Hua-lin Fan; Li-huan Zeng; Wei Guo; Lei Jiang; Xue-biao Wei; Wen-fei He; Sha Tao; Zhi-qiang Guo; Ji-yan Chen; et al. (European Journal of Clinical Pharmacology, 2020)

Biogenic silica concentration as a marine primary productivity proxy in the Holsteinsborg Dyb, West Greenland, during the last millennium - Longbin Sha; Dongling Li; Yanguang Liu; Bin Wu; Yanni Wu; Karen Luise Knudsen; Zhongqiao Li; Hao Xu (Acta Oceanologica Sinica, 2020)

Novel Magnetic Pomelo Peel Biochar for Enhancing Pb(II) And Cu(II) Adsorption: Performance and Mechanism - Yaoning Chen; Yihuan Liu; Yuanping Li; Yanrong Chen; Yanxin Wu; Hui Li; Sha Wang; Zhen Peng; Ran Xu; Ziping Zeng (Water, Air, & Soil Pollution, 2020)

The role of HINT1 in methamphetamine-induced behavioral sensitization - Peng Liu; Gang Lei; Zheng Chu; Li-sha Deng; Liu Yang; Jun-liang He; Yong-hui Dang (Psychopharmacology, 2020)

Carbon material–immobilized ionic liquids were applied on absorption of Hg2+ from water phase - Lihan Sun; Mengru Wang; Wei Li; Sha Luo; Yan Wu; Chunhui Ma; Shouxin Liu (Environmental Science and Pollution Research, 2020)

Inhibition of glycolysis ameliorate arthritis in adjuvant arthritis rats by inhibiting synoviocyte activation through AMPK/NF-кB pathway - Ying Wang; Hao Xian; Jiajia Qi; Fang Wei; Xiu Cheng; Sha Li; Qing Wang; Zhaoyang Liu; Yun Yu; Jing Zhou; Xiaojin Sun; Hao Liu; et al. (Inflammation Research, 2020)

An Injectable Nanocomposite Hydrogel for Potential Application of Vascularization and Tissue Repair - Yilei Ding; An-sha Zhao; Tianmei Liu; Ya-nan Wang; Yuan Gao; Jing-an Li; Ping Yang (Annals of Biomedical Engineering, 2020)

Effect of combining urea fertilizer with P and K fertilizers on the efficacy of urease inhibitors under different storage conditions - Zhipeng Sha; Tiantian Lv; Maarten Staal; Xin Ma; Zhang Wen; Qianqian Li; Gregor Pasda; Tom Misselbrook; Xuejun Liu (Journal of Soils and Sediments, 2020)

Identifying common genome-wide risk genes for major psychiatric traits - Sha Liu; Shuquan Rao; Yong Xu; Jun Li; Hailiang Huang; Xu Zhang; Hui Fu; Qiang Wang; Hongbao Cao; Ancha Baranova; Chunhui Jin; Fuquan Zhang (Human Genetics, 2020)

Increased risk of herpes zoster infection in patients with inflammatory bowel disease: a meta-analysis of cohort studies - Longui Ning; Rongqiang Liu; Sha Li; Guodong Shan; Haojie Du; Jie Zhang; Wenguo Chen; Fenming Zhang; Jinghua Yu; Guoqiang Xu (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

TNF-α suppresses sweat gland differentiation of MSCs by reducing FTO-mediated m6A-demethylation of Nanog mRNA - Yihui Wang; Rui Wang; Bin Yao; Tian Hu; Zhao Li; Yufan Liu; Xiaoli Cui; Liuhanghang Cheng; Wei Song; Sha Huang; Xiaobing Fu (Science China Life Sciences, 2020)

Predicting the higher heating value of syngas pyrolyzed from sewage sludge using an artificial neural network - Hongsen Li; Qi Xu; Keke Xiao; Jiakuan Yang; Sha Liang; Jingping Hu; Huijie Hou; Bingchuan Liu (Environmental Science and Pollution Research, 2020)

Energy transition, CO2 mitigation, and air pollutant emission reduction: scenario analysis from IPAC model - Kejun Jiang; Sha Chen; Chenmin He; Jia Liu; Sun Kuo; Li Hong; Songli Zhu; Xiang Pianpian (Natural Hazards, 2019)

Direct and indirect effects of elevated CO2 and nitrogen addition on soil microbial communities in the rhizosphere of Bothriochloa ischaemum - Lie Xiao; Guobin Liu; Peng Li; Sha Xue (Journal of Soils and Sediments, 2019)

Functional characterization of three MATE genes in relation to aluminum-induced citrate efflux from soybean root - Ying Zhou; Zhengbiao Wang; Li Gong; Anle Chen; Ning Liu; Sha Li; Haoran Sun; Zhenming Yang; Jiangfeng You (Plant and Soil, 2019)

Effect of marginal topography around the Tibetan Plateau on the evolution of central Asian arid climate: Yunnan–Guizhou and Mongolian Plateaux as examples - Zhengguo Shi; Yingying Sha; Xiaodong Liu; Xiaoning Xie; Xinzhou Li (Climate Dynamics, 2019)

Deubiquitylatinase inhibitor b-AP15 induces c-Myc-Noxa-mediated apoptosis in esophageal squamous cell carcinoma - Beibei Sha; Xiaoyu Chen; Han Wu; Miaomiao Li; Jianxiang Shi; Longhao Wang; Xingge Liu; Ping Chen; Tao Hu; Pei Li (Apoptosis, 2019)

Synthesis and biological evaluation of novel disulfides incorporating 1,3,4-thiadiazole scaffold as promising antitumor agents - Sha Li; Hai-Xin Wang; Hai-Ying Liu; Fen Jing; Xiao-Yun Fu; Cai-Wen Li; Yan-Ping Shi; Bao-Quan Chen (Medicinal Chemistry Research, 2019)

The associations of air pollution exposure during pregnancy with fetal growth and anthropometric measurements at birth: a systematic review and meta-analysis - Li Fu; Yi Chen; Xinyi Yang; Zuyao Yang; Sha Liu; Lei Pei; Baixiang Feng; Ganxiang Cao; Xin Liu; Hualiang Lin; Xing Li; Yufeng Ye; et al. (Environmental Science and Pollution Research, 2019)

PM2.5 affects establishment of immune tolerance in newborn mice by reducing PD-L1 expression - Li Yan; Caihui Gong; Linyan Ying; Wenlong Fu; Sha Liu; Jihong Dai; Zhou Fu (Journal of Biosciences, 2019)

Cloning, Expression and Characterization of a Highly Active Alcohol Dehydrogenase for Production of Ethyl (S)-4-Chloro-3-Hydroxybutyrate - Yi-Hao Zhu; Cai-Yun Liu; Sha Cai; Li-Bin Guo; In-Won Kim; Vipin C. Kalia; Jung-Kul Lee; Ye-Wang Zhang (Indian Journal of Microbiology, 2019)

Expression of ASIC3 in the Trigeminal Nucleus Caudalis Plays a Role in a Rat Model of Recurrent Migraine - Sha Wang; Bai-Xue Wu; Chao-Yang Liu; Guang-Cheng Qin; Wen-Hui Yan; Ji-Ying Zhou; Li-Xue Chen (Journal of Molecular Neuroscience, 2018)

The influence of drought strength on soil respiration in a woody savanna ecosystem, southwest China - Yuntong Liu; Jing Li; Yanqiang Jin; Yiping Zhang; Liqing Sha; John Grace; Qinghai Song; Wenjun Zhou; Aiguo Chen; Peiguang Li; Shubin Zhang (Plant and Soil, 2018)

Global environmental costs of China's thirst for milk - Zhaohai Bai; Michael R. F. Lee; Lin Ma; Stewart Ledgard; Oene Oenema; Gerard L. Velthof; Wenqi Ma; Mengchu Guo; Zhanqing Zhao; Sha Wei; Shengli Li; Xia Liu; et al. (Global Change Biology, 2018)
China has an ever‐increasing thirst for milk, with a predicted 3.2‐fold increase in demand by 2050 compared to the production level in 2010. What are the environmental implications of meeting this demand, and what is the preferred pathway? We addressed these questions by using a nexus approach, to examine the interdependencies of increasing milk consumption in China by 2050 and its global impacts, under different scenarios of domestic milk production and importation. Meeting China's milk demand in a business as usual scenario will increase global dairy‐related (China and the leading milk exporting regions) greenhouse gas ( GHG ) emissions by 35% (from 565 to 764 Tg CO 2eq ) and land use for dairy feed production by 32% (from 84 to 111 million ha) compared to 2010, while reactive nitrogen losses from the dairy sector will increase by 48% (from 3.6 to 5.4 Tg nitrogen). Producing all additional milk in China with current technology will greatly increase animal feed import; from 1.9 to 8.5 Tg for concentrates and from 1.0 to 6.2 Tg for forage (alfalfa). In addition, it will increase domestic dairy related GHG emissions by 2.2 times compared to 2010 levels. Importing the extra milk will transfer the environmental burden from China to milk exporting countries; current dairy exporting countries may be unable to produce all additional milk due to physical limitations or environmental preferences/legislation. For example, the farmland area for cattle‐feed production in New Zealand would have to increase by more than 57% (1.3 million ha) and that in Europe by more than 39% (15 million ha), while GHG emissions and nitrogen losses would increase roughly proportionally with the increase of farmland in both regions. We propose that a more sustainable dairy future will rely on high milk demanding regions (such as China) improving their domestic milk and feed production efficiencies up to the level of leading milk producing countries. This will decrease the global dairy related GHG emissions and land use by 12% (90 Tg CO 2eq reduction) and 30% (34 million ha land reduction) compared to the business as usual scenario, respectively. However, this still represents an increase in total GHG emissions of 19% whereas land use will decrease by 8% when compared with 2010 levels, respectively.

A 3-D DDA damage analysis of brick masonry buildings under the impact of boulders in mountainous areas - Shu-guang Liu; Zhu-jun Li; Hong Zhang; Wei Wu; Gui-hui Zhong; Sha Lou (Journal of Mountain Science, 2018)

Mechano growth factor E peptide inhibits invasion of melanoma cells and up-regulates CHOP expression via endoplasmic reticulum stress - Jianhua He; Lili Dong; Kang Xu; Yuna Qian; Chunli Wang; Yongqiang Sha; Juila Li Zhong; Wanqian Liu; Yonggang Lv; Yang Song; Li Yang (Biotechnology Letters, 2018)

Comparison of infrared canopy temperature in a rubber plantation and tropical rain forest - Qing-Hai Song; Yun Deng; Yi -Ping Zhang; Xiao-Bao Deng; You-Xing Lin; Li-Guo Zhou; Xue-Hai Fei; Li-Qing Sha; Yun-Tong Liu; Wen-Jun Zhou; Jin-Bo Gao (International Journal of Biometeorology, 2017)

Electrophysiologic Studies on the Risks and Potential Mechanism Underlying the Proarrhythmic Nature of Azithromycin - Mengdan Zhang; Ming Xie; Sha Li; Ying Gao; Shuyin Xue; Huili Huang; Kesu Chen; Fuming Liu; Long Chen (Cardiovascular Toxicology, 2017)

Brain abnormalities in fucosidosis: transplantation or supportive therapy? - Minyan Jiang; Sha Liu; Hua Jiang; Yunting Lin; Yongxian Shao; Hao Hu; Xiaoyuan Zhao; Hongsheng Liu; Yonglan Huang; Li Liu (Metabolic Brain Disease, 2017)

Pilot-Scale Study on Treating Wastewater from Magnesium-Based Exhaust Gas Cleaning System by a Novel Process - Tie Li; Lin Sha; Quan Liu; Jiao Zhao; Xiaojia Tang; Yimin Zhu (Water, Air, & Soil Pollution, 2017)

Fatality risks for nosocomial outbreaks of Middle East respiratory syndrome coronavirus in the Middle East and South Korea - Jianping Sha; Yuan Li; Xiaowen Chen; Yan Hu; Yajin Ren; Xingyi Geng; Zhiruo Zhang; Shelan Liu (Archives of Virology, 2017)

Induced Pluripotent Stem Cells in Huntington’s Disease: Disease Modeling and the Potential for Cell-Based Therapy - Ling Liu; Jin-Sha Huang; Chao Han; Guo-Xin Zhang; Xiao-Yun Xu; Yan Shen; Jie Li; Hai-Yang Jiang; Zhi-Cheng Lin; Nian Xiong; Tao Wang (Molecular Neurobiology, 2016)

Prescreening, identification and harvesting of microalgae with antibacterial activity - Ang Li; Ling Zhang; Zhen-yu Zhao; Sha-sha Ma; Meng Wang; Ping-huai Liu (Biologia, 2016)

Enhancement of Pork Jerky Using Co-cultures of Lactobacillus bulgaricus and Angel Yeast - Changqing Zhao; Ziyang Lu; Jing Huang; Sha He; Hui Tan; Gang Wang; Dayu Liu; Yubin Li (Indian Journal of Microbiology, 2016)

The association between the ring finger protein 213 (RNF213) polymorphisms and moyamoya disease susceptibility: a meta-analysis based on case–control studies - Xun-Sha Sun; Jun Wen; Jiao-Xing Li; Rong Lai; Yu-Fang Wang; Hui-Jiao Liu; Wen-Li Sheng (Molecular Genetics and Genomics, 2016)

Microsatellite records for volume 8, issue 2 - Dareen Almojil; Maria Cristina Arias; Rochelle R. Beasley; Yiyong Chen; Rulon W. Clark; Yinghui Dong; Zhiguo Dong; Natalie Forsdick; Elaine Françoso; E. González-Ortegón; A. M. González-Tizón; Linsheng Gui; et al. (Conservation Genetics Resources, 2016)

Response of Soil Moisture to Hydro-meteorological Variables Under Different Precipitation Gradients in the Yellow River Basin - Sha Li; Wei Liang; Weibin Zhang; Qinghua Liu (Water Resources Management, 2016)

Antigenic variation of the human influenza A (H3N2) virus during the 2014–2015 winter season - Sha Hua; XiYan Li; Mi Liu; YanHui Cheng; YouSong Peng; WeiJuan Huang; MinJu Tan; HeJiang Wei; JunFeng Guo; DaYan Wang; AiPing Wu; YueLong Shu; et al. (Science China Life Sciences, 2015)

Palaeo-sea-ice changes on the North Icelandic shelf during the last millennium: Evidence from diatom records - LongBin Sha; Hui Jiang; YanGuang Liu; MeiXun Zhao; DongLing Li; ZhenLou Chen; Yun Zhao (Science China Earth Sciences, 2015)

Establishment and characterization of a gonad cell line from half-smooth tongue sole Cynoglossus semilaevis pseudomale - Ai Sun; Song-Lin Chen; Feng-Tao Gao; Hai-Long Li; Xiao-Feng Liu; Na Wang; Zhen-Xia Sha (Fish Physiology and Biochemistry, 2015)

Estimation of contribution ratios of pollutant sources to a specific section based on an enhanced water quality model - Bibo Cao; Chuan Li; Yan Liu; Yue Zhao; Jian Sha; Yuqiu Wang (Environmental Science and Pollution Research, 2015)

Impaired erythrocyte deformability in transgenic HO-1G143H mutant mice - Gan Chen; Yujing Yin; Bo Wang; Penglong Li; Qingjun Liu; Guoxing You; Jingxiang Zhao; Sha Xia; Lian Zhao; Hong Zhou (Transgenic Research, 2015)

From Inducing Autophagy to Programmed Cell Death? The PI3K Functional Domain Study of Protein Latcripin-1 from Lentinula edodes C91-3 - Ben Liu; Siruo Zhang; Mintao Zhong; Li Sha; Yongzhi Lun; Wei Zhang; Xiaoli Wang; Xingyun Li; Jing Cao; Anhong Ning; Min Huang (International Journal of Peptide Research and Therapeutics, 2014)

Dynamic alterations of connexin43, matrix metalloproteinase-2 and tissue inhibitor of matrix metalloproteinase-2 during ventricular fibrillation in canine - Jing Wang; Jing-sha Li; Hong-zhen Liu; Shao-lei Yi; Guo-ying Su; Yun Zhang; Jing-quan Zhong (Molecular and Cellular Biochemistry, 2014)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

Cloning and expression analysis of a novel high-mobility group box 2 homologue from Lampetra japonica - Pang Yue; Xiao Rong; Xue Zhuang; Huang Jin Sha; Jin Min Li; Liu Xin; Qing Wei Li (Fish Physiology and Biochemistry, 2014)

Immunologic Mechanism of Patchouli Alcohol Anti-H1N1 Influenza Virus May Through Regulation of the RLH Signal Pathway In Vitro - Xian-Lin Wu; Da-Hong Ju; Jia Chen; Bin Yu; Kang-Li Liu; Jin-Xiong He; Cong-Qi Dai; Sha Wu; Zhou Chang; You-Ping Wang; Xiao-Yin Chen (Current Microbiology, 2013)

Erratum to: Synergistic effect and mechanism of vitamin A and vitamin D on inducing apoptosis of prostate cancer cells - Jianjun Sha; Jiahua Pan; Ping Ping; Hanqing Xuan; Dong Li; Juanjie Bo; Dongming Liu; Yiran Huang (Molecular Biology Reports, 2013)

Synergistic effect and mechanism of vitamin A and vitamin D on inducing apoptosis of prostate cancer cells - Jianjun Sha; Jiahua Pan; Ping Ping; Hanqing Xuan; Dong Li; Juanjie Bo; Dongming Liu; Yiran Huang (Molecular Biology Reports, 2013)

Genome-wide association study identified novel genetic variant on SLC45A3 gene associated with serum levels prostate-specific antigen (PSA) in a Chinese population - Jielin Sun; Sha Tao; Yong Gao; Tao Peng; Aihua Tan; Haiying Zhang; Xiaobo Yang; Xue Qin; Yanling Hu; Junjie Feng; Seong-Tae Kim; Xiaoling Lin; et al. (Human Genetics, 2013)

A fully automatic registration approach based on contour and SIFT for HJ-1 images - XiLiang Ni; ChunXiang Cao; Lin Ding; Tao Jiang; Hao Zhang; HuiCong Jia; GuangHe Li; Jian Zhao; Wei Chen; Wei Ji; Min Xu; MengXu Gao; et al. (Science China Earth Sciences, 2012)

Preparation of Rotigotine-Loaded Microspheres and Their Combination Use with L-DOPA to Modify Dyskinesias in 6-OHDA-Lesioned Rats - Aiping Wang; Lexi Wang; Kaoxiang Sun; Wanhui Liu; Chunjie Sha; Youxin Li (Pharmaceutical Research, 2012)

Electrophysiologic Characteristics of the Crista Terminalis and Implications on Atrial Tachycardia in Rabbits - Jin Li-jun; Liu Xue-yin; Huang Cong-xin; Yang Bo; Yang Sha-ning; Wu Gang; Xie Qiang; Liu Huang-jun (Cell Biochemistry and Biophysics, 2012)

Quantitative estimation of the shrub canopy LAI from atmosphere-corrected HJ-1 CCD data in Mu Us Sandland - Wei Chen; ChunXiang Cao; QiSheng He; HuaDong Guo; Hao Zhang; RenQiang Li; Sheng Zheng; Min Xu; MengXu Gao; Jian Zhao; Sha Li; XiLiang Ni; et al. (Science China Earth Sciences, 2010)

Depositional environment in the southern Ulleung Basin, East Sea (Sea of Japan), during the last 48 000 years - Yanguang Liu; Longbin Sha; Xuefa Shi; Bong-Chool Suk; Chaoxin Li; Kunshan Wang; Xiaoyan Li (Acta Oceanologica Sinica, 2010)

Lack of association between ADRA2B -4825 gene insertion/deletion polymorphism and migraine in Chinese Han population - Jian-Qiang Ni; Sha-Sha Jia; Min Liu; Shou-Gong Chen; Yu-Ting Jiang; Wan-Li Dong; Yu-Zhen Gao (Neuroscience Bulletin, 2010)

Generation and analysis of 10 000 ESTs from the half‐smooth tongue sole Cynoglossus semilaevis and identification of microsatellite and SNP markers - Z. Sha; S. Wang; Z. Zhuang; Q. Wang; Q. Wang; P. Li; H. Ding; N. Wang; Z. Liu; S. Chen (Journal of Fish Biology, 2010)
Three normalized cDNA libraries were constructed, two of which were constructed from reproductive tissues ovary and testis, and the other one from pooled immune tissues including head kidney, intestine, liver and spleen. A total of 10 542 clones were sequenced generating 10 128 expressed sequence tags (ESTs). Cluster analysis indicated a total of 5808 unique sequences including 1712 contigs and 4096 singletons. A total of 4249 (73%) of the unique ESTs had significant hits to the non‐redundant protein database, 2253 of which were annotated using Gene Ontology (GO) terms. A total of 311 microsatellites (with 246 having sufficient flanking sequences for primer design) and 6294 putative SNPs were identified. These genome resources provide the material basis for future microarray development, marker validation and genetic linkage and QTL analysis.

Blockade of HERG K+ channel by isoquinoline alkaloid neferine in the stable transfected HEK293 cells - Dong-fang Gu; Xue-lian Li; Zhi-ping Qi; Sha-shan Shi; Mei-qin Hu; Dong-min Liu; Cheng-bai She; Yan-jie Lv; Bao-xin Li; Bao-feng Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Association of the DRD2 and DRD3 polymorphisms with response to pramipexole in Parkinson’s disease patients - Ying-Zi Liu; Bei-Sha Tang; Xin-Xiang Yan; Jie Liu; Dong-Sheng Ouyang; Li-Nuo Nie; Lan Fan; Zhi Li; Wei Ji; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Determination of Bioactive Matter by Affinity Adsorption Solid Substrate–Room Temperature Phosphorimetry Based on Lectin Labeled with Self-ordered Ring of Eosin Y - Jia-Ming Liu; Zhen-Bo Liu; Wen-Qi Li; Xiao-Mei Huang; Li-Qing Zeng; Jian Sha; Fei-Ming Li (Journal of Fluorescence, 2009)

NYD-SP15: A Novel Gene Potentially Involved in Regulating Testicular Development and Spermatogenesis - Qinghuai Liu; Jin Liu; Qinhong Cao; Jiahao Sha; Zuomin Zhou; Hui Wang; Jianmin Li (Biochemical Genetics, 2006)

A new nor-lignan from the seeds of Descurainia sophia - Kai Sun; Xian Li; Wen Li; Jian-Ming Liu; Jin-Hui Wang; Yi Sha (Natural Product Research, 2006)